GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 652473151 species occurrences available in GBIF matching the query: All data. The dataset includes 652473151 records from 13621 constituent datasets: 1 records from Zetes rubens. 246 records from Berkel. 979 records from Herbier_CNSF. 348268 records from BioFokus. 1445 records from Shellfish (GNHM-MS). 2 records from uno city. 19 records from Landesgartenschau. 19219 records from Oregon State Ichthyology Collection. 794 records from Irish Deer Database. 1500102 records from Garden Bird Surveys. 321 records from Collection Mammalogie - ZSRO. 1014 records from JOIw - Xiloteca Joinvillea. 1 records from Hoplophora globosa. 20 records from Heteroptera - SMNG. 126294 records from UAM Mammal Collection (Arctos). 105 records from Birdrace-ARKONAuten-Rügen. 72 records from Birdrace-Buteo2DO-Dortmund. 76 records from Birdrace-Birding_for_Nature-Bonn. 71 records from Birdrace-NAJU_Aspach-Rems/Murr. 59 records from Im Bauerngarten. 74 records from Birdrace_Gätkes_Schergen-Helgoland. 54 records from Park Schönfeld (Kassel). 13 records from FND "Weißer Berg" Leißling. 3 records from FFR Hausen. 21 records from LBV-Kindergruppen Markt Tussenhausen. 144 records from VFD-RP: Hunsrück: Pferdeweide Kucher. 54 records from Biotope im Schulumfeld. 99 records from Streuobstwiese Stedar. 194 records from Bodenteicher Seewiesen. 877161 records from Finnish Winter Bird Census. 461 records from Collection Lepidoptera SMF. 11806 records from Hymenoptera de la Colección Entomológica del Instituto Alexander von Humboldt. 53985 records from BioMar - LIFE project. 798 records from (Appendix Table 3) Relatice abundances of planktonic foraminiferal species in sediment core MD01-2390. 1003 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 239449 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 670 records from (Table 1) Abundance of Miocene to Pleistocene dinoflagellate cysts in ODP Hole 133-815A. 46664 records from The Scottish Ornithologists' Club - Fife non-breeding bird 5km atlas 1991-99. 3633 records from Bioimages. 1326 records from (Table T9) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zones P5-P7. 7076556 records from Great Backyard Bird Count. 16 records from Scorpaena bulacephala, a new species of scorpionfish (Scorpaeniformes: Scorpaenidae) from the northern Tasman Sea.. 65 records from Revalidation and redescription of Pterocryptis anomala (Herre, 1933), a catfish (Teleostei: Siluridae) from southern China.. 1 records from Arthropoden aus südostalpinen Höhlen.. 116410 records from Naturalis Biodiversity Center (NL) - Crustacea. 6 records from Hemichordata collection of National Museum of Nature and Science. 129 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 5549 records from Diplopoda (NSMK-DI). 97 records from DMNH Eggs. 336 records from Especies de Anacroneuria (Insecta: Plecoptera: Perlidae) de Colombia, depositadas en el Museo de Entomología de la Universidad del Valle (Cali, Colombia). 865 records from (Appendix C) Benthic foraminifera extinction group species in DSDP Site 80-548. 31917 records from Mollusca of Costa Rica (INBio). 8857 records from Artròpodes d'Andorra. 3 records from Revision der Ceratozetidae, 3. Ceratozetes laticuspidatus n. sp. (Arach., Acari, Oribatei). 227 records from Colección de Salamandras Museo de La Salle Bogotá (MLS). 373 records from Otter survey of Ireland 2004 & 2005. 468 records from Chironomid Specimen records in the Chironomid DNA Barcode Database. 3597 records from (Table T1) Planktonic foraminifera stratigraphy of ODP Hole 198-1209C sediments. 71 records from Occurrence data of Ectyphus and Parectyphus (Diptera: Asiloidea: Mydidae). 10730 records from kpabg_lichens. 156156 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 7 records from Peckoltia sabaji, a new species from the Guyana Shield (Siluriformes: Loricariidae).. 777113 records from Australian National Herbarium (CANB). 775 records from A catalogue of the fishes held in the Istanbul University, Science Faculty, Hydrobiology Museum.. 97 records from (Table 1) Distribution of calcareous nannofossils in ODP Hole 167-1017E sediments. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 216 records from Registros biológicos del Humedal Santa Maria del Lago 1999-2013. 398 records from Tsetse flies of East Africa update. 375 records from Phthiraptera. 993 records from Rossendale Ornithologists' Club - ROC RSPB Farmland Species Survey Dataset. 153480 records from Molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 58475 records from Oregon State University Herpetological Collection. 8748 records from British Lichen Society - BLS Rare and Threatened Lichen Records: Wales. 104 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cathartidae. 57218 records from National Biodiversity Data Bank. Observation records, 1900-2014. 27988 records from Argyll Bird Club - Bird records for Argyll for the years 2002 and 2003. 3367 records from (Figure 4) Distribution of dinoflagellate cysts in the Albian/Cenomanian of DSDP Hole 79-547A. 139 records from The Bat Conservation Trust - Woodland Survey. 123 records from Bryozoa of the British Isles. 3105 records from The Vascular Plants Collection of the Regensburgische Botanische Gesellschaft. 10512 records from (Table T2) Plankontic foraminifera stratigraphy of ODP Hole 184-1146A. 18 records from Rita macracanthus, a new riverine catfish (Teleostei: Bagridae) from South Asia.. 48944 records from Grey seal at-sea distribution 2009-2014. 16 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rostratulidae. 6543 records from University of Ghent - Zoology Museum - Vertebratacollectie. 2356 records from Naturalis National Natural History Museum (NL) – Aves_Types. 2312 records from Mycological collection of the National Museum. 336 records from Macroarthropods, Isua 2013, Greenland. 155 records from (Appendix 1) Coral analysis and isostatic rebound effects from different Holes of IODP Expedition 310. 468533 records from Royal Dutch Angling Association (SVN) - Piscaria. 1311 records from (Table 3A) Occurrence and estimated abundance of planktonic foraminifers at DSDP Holes 85-572 and 85-572A. 1 records from Nothrus spinifer. 2707 records from Colección de Coleoptera (Scarabaeoidea) del sureste de la Península Ibérica de la Universidad de Granada. 43 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Spheniscidae. 1485 records from IWDG Constant Effort Cetacean Sighting Scheme. 100 records from Royal Horticultural Society - Nezara viridula records held by the Royal Horticultural Society. 118 records from A Tenebrionid beetle’s dataset (Coleoptera, Tenebrionidae) from Peninsula Valdés (Chubut, Argentina). 6060 records from Free-living Nematodes from Patagonia coastal lagoons (Chubut, Santa Cruz, Argentina).. 73514 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 2 records from (Table 10) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-854B. 273 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 322-C0012A. 36 records from Two new species of Isbrueckerichthys Derijst, 1996 (Siluriformes: Loricariidae) from the rio Paranapanema basin, Brazil.. 12161 records from ISE - Herbário ISE. 1352 records from (Figure 9) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-536. 115 records from USGS SESC - Virgin Islands - Herpetofauna - 2001-2002. 380 records from USGS SESC - Biscayne - Herpetofauna - 2002-2003. 67914 records from HUFU - Herbarium Uberlandense. 2 records from The first record of a fly of the family Milichiidae (Diptera) interacting with an ant of the genus Polyrhachis Smith, 1857 (Hymenoptera: Formicidae). 5 records from Arthropoden aus südostalpinen Höhlen.. 5953 records from SPFw - Xiloteca do Instituto de Biociências da Universidade de São Paulo. 215 records from The Diptera Site. 475 records from Equinodermos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMeq-UV). 132 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 322-C0011B. 396 records from RSPB - 2008 Farmland Bird Survey North East Wales - RSPB/CCW. 315232 records from Naturalis Biodiversity Center (NL) - Hymenoptera. 10072 records from Guadeloupe_Herbier. 1252 records from Aquatic Coleoptera Conservation Trust - SNH site condition monitoring of SSSIs for water beetles 2010. 28385 records from Plan de vertebrados de la Patagonia. 108 records from (Table 3) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-844B. 338 records from (Tab. 9.C) Presence and abundance of benthic fauna at station FINO 1 in 2005-2007. 6848 records from Ratti Master Thesis / Fraser Valley, British Columbia. 2661 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Tayrona. 3 records from A new species of the genus Ectemnius Dahlbom, 1845 from Cameroon (Hymenoptera: Crabronidae). 385 records from (Appendix E) Size measurements of Selenopemphix undulata sp. nov. in ODP Site 202-1233. 24 records from A revision of the Indo-Pacific fish genus Caragobius (Gobiidae: Amblyopinae).. 457 records from Royal Horticultural Society - European Pear Rust (Gymnosporangium sabinae) monitoring. 1957 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD unverified freshwater fish data up to current day. 2 records from Oribatids from Switzerland I. (Acari: Oribatida). (Acarologica Genavensia LXXXI). 2 records from Benthic hard-bottom communities abundance at X-Huinay in 2010. 201 records from Microplankton abundance measured on water bottle samples during AEGAEO cruise LIA-7. 57 records from The Game & Wildlife Conservation Trust - Capercaillie sightings Speyside 2011. 83 records from Eden Rivers Trust - White-clawed crayfish (Austropotamobius pallipes) distributions within four sub-catchments of the River Eden Catchment, Cumbria 2007-2008. 1904 records from Terrestrial Heteroptera Recording Scheme (Shieldbugs & allied species) - Flickr (01) Shieldbugs & allied species. 13242 records from JOI - Herbário Joinvillea. 30 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto1-10. 277 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 2925 records from Herbarium specimens of the Muséum d'Histoire Naturelle d'Autun (AUT). 10030 records from Free-living marine Nematodes from San Julián bay (Santa Cruz, Argentine), 2009.. 1 records from Über einige von Jaroslav Storkán in Bulgarien gesammelte Chilopoden. 231 records from (Appendix A) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 107-654A. 238 records from Seven new species of Spathidexia Townsend (Diptera: Tachinidae) reared from caterpillars in Area de Conservación Guanacaste, Costa Rica. 20 records from Truchas Mexicanas. 19 records from Inventario de Aves Pauto J, Yopal, Casanare. 113 records from Studies on species of Holarctic Pardosa groups (Araneae, Lycosidae). VII. The Pardosa tesquorum group. 3 records from MSB Mammal Observations (Arctos). 279 records from Dieta del Piquero Café (Sula leucogaster etesiaca) en el Parque Nacional Natural Gorgona, Pacífico colombiano.. 2494 records from Colección de peces dulceacuícolas de Costa Rica. 1650 records from University of Calgary Herbarium. 27 records from Redescription of Apteronotus mariae (Eigenmann & Fisher, 1914) and the taxonomic status of Apteronotus jurubidae (Fowler, 1944) (Gymnotiformes: Apteronotidae).. 3509 records from Entocytheridae (Ostracoda) World Database. 31 records from Siphonaptera. 8220356 records from OEH Atlas of NSW Wildlife. 457 records from Microbial Observatory of the Laboratoire Arago. 99300 records from Landesmuseum Kärnten. 4 records from Taxonomy of Afrotropical and West Palaearctic ants of the ponerine genus Hypoponera Santschi (Hymenoptera: Formicidae).. 401 records from (Fig. 7) Coccolith species abundance of sediment core GeoB11035-1. 5796 records from Real Jardin Botanico: Dibujos de la Real Expedición Botánica del Nuevo Reino de Granada (1783-1816), dirigida por J.C. Mutis. 164 records from EcoRecord - Reptile records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 15 records from Taxonomy of European Damaeidae (Acari: Oribatida) I. Kunstidamaeus Miko, 2006, with comments on Damaeus sensu lato. 8934780 records from Botanical Society of the British Isles - Vascular Plants Database. 1 records from Celaeno plicata. 160 records from Scottish Natural Heritage - Distribution of Scottish wildcats (Felis silvestris) in Scotland (2006-2008) â database extract (breeding and non-breeding records). 1152 records from (Table 12) Benthic foraminifera in Eocene-Oligocene sediments of DSDP Hole 90-592. 74 records from (Table 3) Abundance of benthic foraminifera and ostracoda in bottom sediments from the Ashadze-1 Hydrothermal Field. 58 records from (Table 4a) Range chart of benthic and planktonic foraminifera of ODP Hole 127-796A. 66 records from (Table T8) Calcareous nannofossil stratigraphy of ODP Hole 198-1211A. 33 records from Revision von Suctobelba trigona (Michael, 1888). 8 records from Dendrogramma, New Genus, with Two New Non- Bilaterian Species from the Marine Bathyal of Southeastern Australia (Animalia, Metazoa incertae sedis) – with Similarities to Some Medusoids from the. 172345 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine) data for Great Britain and Ireland. 32 records from Abyssal fauna of the UK-1 polymetallic nodule exploration claim, Clarion-Clipperton Zone, central Pacific Ocean: Echinodermata. 130 records from (Table S1) Pb/U zircon ages of ODP Hole 118-735B. 51110 records from Inventaire National du Patrimoine Naturel : Insectes Orthoptères de France. 2 records from Enchelycore nycturanus, a new moray eel from South Africa (Teleostei: Anguilliformes: Muraenidae).. 9543 records from RSPB - Wader survey on Uist in 2007 (RSPB/BTO). 690 records from Mid Ulster Hare Surveys 2012-2015. 7478 records from Merseyside BioBank - North Merseyside Reptiles and Amphibians (unverified). 12279 records from ISM Mammalogy Collection. 330041 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 10 records from (Table C) Fauna associated with Bathymodiolus azoricus mussel beds within the Rainbow hydrothermal field, Mid-Atlantic Ridge. 129 records from (Table 2) Planktonic foraminifer abundance in ODP Section 167-1021C-10H-2. 1741 records from EcoRecord - Mollusc records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 191 records from Herpetofauna laguna El Tinije. 31936 records from Records of Avifauna of Wetlands around Keoladeo National Park, Bharatpur, India. 1238 records from Insect Collection (CeStuBio). 83 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Polioptilidae. 21975 records from HUEM - Herbário da Universidade Estadual de Maringá. 477 records from Visfauna - Juvenile and adult fishes in riparian habitats along the river Leie in Flanders, Belgium. 7735 records from CSUC Vertebrate Collection. 1334 records from (Table 5) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-848B. 41 records from Two new species of Pseudoscopelus (Teleostei: Chiasmodontidae), with a new diagnosis for the genus.. 9 records from A new species of the genus Aphanius (Nardo, 1832) (Actinopterygii, Cyprinodontidae) from Algeria.. 1030627 records from Phanerogamic Botanical Collections (S). 10000 records from National Lesser Horseshoe Bat Database. 37 records from Museu Paraense Emilio Goeldi - Schizomida Collection. 90189 records from African Rodentia. 1988 records from (Appendix 2) Benthic foraminifera in ODP Hole 160-963A. 14379 records from CSIRO, South East Fishery Habitat Ecosystem Study, Southeast Australia, 1993-1997. 5729 records from Alterra (NL) - Entomofauna inventory in cattle grazed dune grassland. 244 records from Scottish Natural Heritage - The ecology of Najas flexilis (Slender naiad). 1 records from Pollen analysis of sediment profile KAIX_B from Kaiserwinkel. 1 records from Un chilopode cavernicole nouveau de Yougloslavie Bothropolys magnificus n. sp.. 62283 records from PRECIS (KwaZulu-Natal Herbarium). 5709 records from Coleoptera of Piska Forest. 712 records from Herbier G. Garapin (BOUM). 4108 records from Anthomyiidae Study Group - Anthomyiidae records for Great Britain. 59016 records from Biological Records Centre - Isopoda (Interim dataset). 2418 records from (Figure 9) Distribution of Maaestrichtian planktonic foraminifera in ODP Hole 132-810C. 74 records from Terrestrial gastropods of Srebarna Nature Reserve, North-Eastern Bulgaria ( Gastropoda ). 8 records from A review of the ant genus Metapone Forel from Madagascar.. 35 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2001. 9302 records from Ants from the Paraguayan dry Chaco. 379 records from WNMU Fish Collection (Arctos). 2546 records from The atlas of butterflies in Kraków. 20043 records from Mollusca collection of National Museum of Nature and Science. 250 records from Taxonomic revision of the seasonal South American killifish genus Simpsonichthys (Teleostei: Cyprinodontiformes: Aplocheiloidei: Rivulidae).. 111784 records from Jordal. 268686 records from MVZ Herp Collection (Arctos). 28924 records from Inventory and BioBlitz Records from rare Charitable Research Reserve. 28702 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mammalia. 3 records from Revision of the ant genus Perissomyrmex with notes on the phylogeny of the tribe Myrmecinini.. 5824 records from Visfauna - Juvenile and adult fishes in riparian habitats along the river Yser in Flanders, Belgium. 6992 records from RSPB - Stone-curlew Annual Surveys (RSPB/Natural England). 115324 records from University of Vienna, Institute for Botany - Herbarium WU. 55 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cardinalidae. 1300 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del río Cajambre (Guandal), municipio de Buenaventura, Valle del Cauca. 326 records from Colección nacional de palmas de Colombia - JBQ. 22 records from Anostomoides passionis, a new fish species from rio Xingu, Brasil (Characiformes: Anostomidae).. 610 records from RSPB - Farmland bird database in Dumfries and Galloway, 1999-2010 (RSPB). 4 records from New data on recently described rodent species Paulina's Limestone Rat Saxatilomys paulinae Musser, Smith, Robinson & Lunde, 2005 (Mammalia: Rodentia). 6 records from Review of the genus Metopheltes Uchida, 1932 (Hymenoptera, Ichneumonidae) with description of a new species from Vietnam. 1025 records from (Appendix 2) Absolute abundance of nannofossils in ODP Hole 183-1135A. 78 records from Guyane_française_caféier. 38652 records from Marine species distributions in Irish coastal waters. 3175 records from Centre for Genetic Resources, the Netherlands, Indigenous Trees and Shrubs. 65 records from A new species of Rineloricaria (Siluriformes: Loricariidae) from the Paraná and Uruguay River basins, Misiones, Argentina.. 1 records from Damaeus concolor. 1 records from (Table 4) Thecosomata in ODP Hole 134-831A. 10633 records from Biological Records Centre - Collembola Recording Scheme. 26534 records from The Environmental Sample Collection of the Arthropoda Varia Section at the Zoologische Staatssammlung München. 38543 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD other mammal data up to current day. 154 records from (Table T1) Calcareous nannofossil stratigraphy in ODP Hole 186-1150A sediments. 4198 records from Planktic foraminifera (%) of sediment core MD96-2085. 1353 records from Colección de Entomología - Diptera - Ceratopogonidae. 8136 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Coelenterata. 42 records from (Table 2) Benthic foraminifers at DSDP Hole 72-515A. 980 records from (Table AT7) Planktonic foraminiferal stratigraphy of ODP Hole 182-1132B. 248 records from Millipedes and centipedes in German greenhouses (Myriapoda: Diplopoda, Chilopoda). 420 records from Reptilia Collection of Museum and Institute of Zoology PAS. 60672 records from QLD DERM Coastal Bird Atlas (Trial). 1010 records from Flora vascular de las llanuras aluviales del bajo río Nechí. 23052 records from RSPB - Swift Inventory of Low-Level Screaming Parties in the UK, 2009 (RSPB and Swift Conservation Groups). 167 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Psittacidae. 2147 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 1998 records from Aves de la cuenca media del río Bogotá. 3806 records from USGS SESC - Everglades - Herpetofauna - 2005. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 4 records from First record of Limnatis paluda (Hirudinida, Arhynchobdellida, Praobdellidae) from Kazakhstan, with comments on genetic diversity of Limnatis leeches. 1 records from Nothrus runcinatus. 16444 records from UFG - Herbário da Universidade Federal de Goiás. 5 records from A new species of Simopelta (Hymenoptera: Formicidae: Ponerinae) from Brazil and Costa Rica. 1702 records from BioGIS - Bryophytes - HUJ collections. 1592 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Furnariidae. 5821 records from MFS - Herbário Profª. Drª. Marlene Freitas da Silva. 1710 records from (Table 8E) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 19-4 through 25-5. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 51 records from Towards the conservation of parasitoid wasp species in Canada: Preliminary assessment of Microgastrinae (Hymenoptera: Braconidae). 1205 records from Ecology, structure and dynamics of private plantations of Teak (Tectona grandis Lf) of the Department of the Atlantic (South Benin), 2011. 5248 records from (Figure 2) Range and distribution chart of dinoflagellate cysts recovered from Campanian to Maestrichtian sediments at DSDP Hole 95-612. 304 records from Succession of benthic hard-bottom communities abundance at station Errina2012_IS_solar2. 202 records from Biodiversity Information Service for Powys and Brecon Beacons National Park - Distribution of Impatiens glandulifera Royle along the river Irfon during June 2010. 3592 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Invasive Insecta. 1808 records from University of Amsterdam (NL) - Páramo vegetation research, Ecuador.. 232236 records from MVZ Mammal Collection (Arctos). 10 records from Inventarios de Murciélagos Pauto M, La Primavera, Yopal, Casanare. 159 records from University of Amsterdam (NL) - Páramo vegetation research, Venezuela.. 10 records from Merodoras nheco, new genus and species from Rio Paraguay basin, Brazil (Siluriformes, Doradidae), and nomination of the new subfamily Astrodoradinae.. 3087 records from Herpetile collection, Natural History Museum, University of Oslo. 6239 records from (Figure 1) Distribution of dinoflagellate cysts in the mid-Cretaceous of DSDP Hole 79-545. 70222 records from Dorset Environmental Records Centre - Dorset SSSI Species Records 1952 - 2004 (Natural England). 1 records from Zetes longiusculus. 3204 records from Faunal Inventory of Morysin Nature Reserve. 64 records from Reuniting males and females: redescriptions of Nuisiana arboris (Marples 1959) and Cambridgea reinga Forster & Wilton 1973 (Araneae: Desidae, Stiphidiidae). 89874 records from ecoscope_observation_database. 4251 records from Aves de la cuenca media del río Chambery, Caldas. 288 records from Fungi of Słowiński National Park, Poland. 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 353 records from Coastal and marine species. 184364 records from LACM Entomology Collection. 167 records from Faunistic diversity of spiders (Araneae) in Galichitsa mountain (FYR Macedonia). 142691 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 356 records from Morphologische Daten von Puffinus creatopus. 25 records from Glyptothorax botius (Hamilton, 1822), a valid species of catfish (Teleostei: Sisoridae) from northeast India, with notes on the identity of G. telchitta (Hamilton, 1822).. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 35 records from Osteology and phylogeny of Parioglossus (Teleostei, Gobioidei), with a revised key to the species.. 1020 records from Irish Marine Turtle Database. 34 records from New records in vascular plants alien to Kyrgyzstan. 165 records from Palaeoclimate records over the past 22,000 years of sediment core GeoB10053-7. 10075 records from Nematoda of Costa Rica (INBio). 170316 records from Australian National Wildlife Collection provider for OZCAM. 15181 records from British Lichen Society - BLS Lichen Database: Welsh churchyards. 412 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Columbidae. 4343 records from PolE At Sea Observations of Birds and Marine Mammals during PS 81 (ANT-XXIX/4). 10358 records from Census of the flora of Benin. 897 records from Trichoptera of the UNESCO biosphere reserve of the Palatinate forest / North Vosges (Germany, France). 3103 records from DVPR - Herbário da Universidade Tecnológica Federal do Paraná - Dois Vizinhos. 215 records from (Table 8) Benthic foraminifera genera assemblage at DSDP Section 80-548A-28. 22049 records from Tromsø Museum, Bryophytes. 941 records from (Appendix 1) Benthic foraminifera in eastern equatorial Indian Ocean surface sediments. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 18 records from A new species of Anabarhynchus (Diptera: Therevidae) from an ocean beach in south east Victoria. 8410 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 13597 records from Orthopteroidea. 511 records from Coleoptera of Swierklaniec Forest. 2805 records from Fundación Miguel Lillo - Colección Mamíferos. 859 records from Extra-andean Patagonian Herbarrium -CONICET- Argentina. 15637 records from CCBER Herpetology Collection. 52246 records from IAC - Herbário do Instituto Agronômico de Campinas. 7 records from Additions to the Genus Phyllodesmium, with a Phylogenetic Analysis and its Implications to the Evolution of Symbiosis. 8332 records from Joint Nature Conservation Committee - Scotland Otter Survey Database. 575 records from Aspilota-group (Hymenoptera: Braconidae: Alysiinae) diversity in Mediterranean Natural Parks of Spain. 1020718 records from Consortium of California Herbaria. 38187 records from Online Atlas of vascular plants 2012-2020. 12370 records from GRBGT: Southern Cape Herbarium Specimen Collections (1882-2008). 204 records from (Table 8) Sample mass, sand fraction and relative abundances of planktonic foraminifera in ODP Holes 127-794A and 127-197B. 232 records from (Table A1) Stratigraphic distribution of calcareous nannofossils of ODP Hole 198-1210A. 9788 records from SANT-Lich. 1616 records from Gloucestershire Centre for Environmental Records - Gloucestershire Reptiles. 51390 records from Scottish Wildlife Trust - The Scottish Squirrel Database. 163 records from (Table 4) Benthic foraminifera genera assemblage at DSDP Section 80-548A-11-3. 6 records from (Table 1) Abundance of ciliates, dinoflagellates, nauplii and krill at different stations in the Godthabsfjord. 2480 records from Woodland Condition Survey Group - Plants recorded during the non-SSSI woodland condition survey 2011. 7427 records from Weevils of the Tatra Mts.. 20 records from Marine gastropods and other remains profile from sediment core AV14_K2-3. 1 records from Oribates calcaratus. 8 records from Order Diptera, family Mydidae. 78 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: géneros Saltator & Saltatricula. 88901 records from Naturalis National Natural History Museum (NL) – Insecta_Lepidoptera_SE Asia and other regions. 458185 records from Bird Atlas 2007 - 2011. 2 records from Two New Jumping Spiders of the Genus Chalcoscirtus from China (Araneae: Salticidae). 9 records from The Oribatid Family Phthiracaridae II. Redescription of Phthiracarus laevigatus (C. L. KOCH). 74 records from (Table T5) Cretaceous calcareous nannofossil abundance of ODP Hole 173-1069A. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 561820 records from Bee Biology and Systematics Laboratory. 422 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Hirundinidae. 1 records from Egg capsules of Atlantoraja cyclophora (Regan, 1903) and A. platana (Günther, 1880) (Pisces, Elasmobranchii, Rajidae).. 2 records from Pollen analysis of sediment profile AUL00 from Steeger See. 4734 records from Marine Biological Association - Volunteer sightings data held by the DASSH Data Archive Centre. 119 records from Redescription of Tetramorium forte Forel, 1904 (Insecta: Hymenoptera: Formicidae), a western Mediterranean ant species.. 4 records from Fossil (SMNH-FO). 1603 records from Cambridgeshire & Peterborough Environmental Records Centre - CPERC Recorders day at Waterbeach barracks and airfield. 4424 records from Portuguese Seaweeds. 10102 records from Herbarium Vonderau - FULD. 13583 records from Highland Biological Recording Group - HBRG Fungus, Lichen and Lower Plants Dataset. 9836 records from Censo de aves acuáticas invernantes de la Comunidad Autónoma del País Vasco. 2 records from A new phreatic catfish of the genus Phreatobius Goeldi 1905 from groundwaters of the Itenez River, Bolivia (Siluriformes: Heptapteridae).. 66 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Aramidae. 35325 records from Bryophyta collection of the Botanical Museum of the University of Oulu. 121225 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 2 records from Postia alni Niemelä & Vampola (Basidiomycota, Polyporales) – member of the problematic Postia caesia complex – has been found for the first time in Hungary. 42659 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Aves. 2 records from Scottish Natural Heritage - Survey of White-clawed crayfish Austropotamobius pallipes in Scotland. 4579 records from Herbarium WRSL, Flora of the Silesia. 145 records from (Tab. 9.B) Presence and abundance of benthic fauna at station FINO 1 in 2005-2007. 26375 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 1172 records from (Table T1) Benthic foraminfera stratigraphy of ODP Hole 199-1215A sediments. 3082 records from dec2011. 2007 records from Palaeobiology collection, FAU Erlangen. 568 records from Coleccion Paleoinvertebrados CCT Mendoza - CONICET. 9 records from Polyrhachis (Myrma) cyaniventris F. Smith, 1858 (Hymenoptera: Formicidae) and a related new ant species from the Philippines.. 1284 records from Collection of Heteroptera. 528 records from Revision of the Malagasy genus Trichoteleia Kieffer (Hymenoptera, Platygastroidea, Platygastridae) - Darwin Core Archives. 1 records from A new species of Cottunculus (Teleostei: Psychrolutidae) from the Mid Atlantic Ridge.. 304 records from John Muir Trust - Bryophytes of Glen Nevis Woods 1987-1988. 768 records from (Table 3) Benthic foraminifera in Southwest Indian Ocean surface sediments. 26 records from Description of a new cyprinid species, Labeo meroensis n. sp. (Teleostei: Cyprinidae), from the River Nile.. 177466 records from CAS Entomology (ENT). 233 records from Dataset for Review of Mimosticus Sharp (Coleoptera: Staphylinidae). 810 records from HTSA-Carpoteca - Carpoteca do Trópico Semiárido. 3 records from A distinctive new species of gnatcatcher in the Polioptila guianensis complex (Aves, Polioptilidae) from western Amazonian Brazil. 8007 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 359 records from Herbarium Senckenbergianum (GLM) - Lichenes. 22804 records from TCWC Marine Invertebrates. 122 records from A taxonomic revision of the catshark genus Haploblepharus Garman 1913 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 36432 records from RSPB - Corncrake national surveys - raw data (SCARABBS). 28626 records from SANT-Algae. 3503 records from CSIRO, Cruise SS200705, Benthic Biodiversity, Northwest Australia, 2007. 6541 records from Likona Invertebrates. 55376 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 5581 records from (Table S3) Significant benthic foraminifera species in ODP Hole 164-994C. 3 records from First record of the genus Leptanilloides (Hymenoptera: Formicidae: Dorylinae) from the United States. 41 records from (Table T5) Calcareous nannofossil abundance of ODP Hole 189-1172A sediments. 44 records from New and poorly known Holarctic species of Boletina Staeger, 1840 (Diptera, Mycetophilidae). 476 records from Caracterización Aves IAI-GAICA: Proyecto Cambio Climático. 25 records from (Table 1) Osmium isotope ratios and Re-Os element content in bulk sediments of ODP Hole 121-758A. 1404059 records from AntWeb. 834 records from Diptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 5733 records from Small Mammal Research Database. 182 records from (Table VII) Benthic foraminifera abundance in the Great Belt Channel. 1 records from Red list project inventory, bryophytes. 2116 records from Collection entomologique Pierre Lachiver. 2 records from Papakula and Hesydrimorpha: how two spider genera were described from the same species collected from the same locality (Araneae: Pisauridae). 35 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rhinocryptidae. 259949 records from Zoology (Museum of Evolution - Uppsala). 32 records from A review of the subfamily Acaenitinae Förster, 1869 (Hymenoptera, Ichneumonidae) from Ukrainian Carpathians. 2258 records from Biological Records Centre - Muscidae (Diptera) records from Britain and Ireland to 1985. 4719911 records from Naturalis Biodiversity Center (NL) - Botany. 62 records from The North American spider genera Paratheridula, Tekellina, Pholcomma and Archerius (Araneae: Theridiidae). 2421 records from BOTUw - Xiloteca "Profa. Dra. Maria Aparecida Mourão Brasil". 1 records from The larva and prepupa of Eupareophora exarmata (Thomson, 1871) (Hymenoptera, Tenthredinidae). 28788 records from EPA River Biologists data. 3 records from A Partial Revision of the Genus Metabelba Grandjean (Oribatei, Acarina). 7251 records from All Ireland Marsh Fritillary Database. 4 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 296072 records from Dr Francis Rose Field Notebook Project - Field Notebook Records of Dr Francis Rose 1950's to 1990's. 19 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 5 records from A new species and records of Diolenius Thorell, 1870 (Araneae: Salticidae) from New Guinea. 4686 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Types. 352 records from Scottish Natural Heritage - Recovery of the medicinal leech Hirudo medicinalis in Scotland - Phase II. 336 records from (Table T3) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones P5-P6b. 1206 records from (Table T3) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1172A sediments. 64 records from Six new species of ants (Insecta: Hymenoptera: Formicidae) from Egypt.. 485 records from National Taiwan Ocean University. 116 records from Concentration of organic-walled dinoflagellate cysts from 116 marine surface samples. 1 records from Lissotes working-group. 1 records from Oribates fuscipes. 100 records from Brock University Herbarium (BU). 1196 records from Entomological collection of the National Museum. 1 records from Zetes cespitum. 13253 records from CHAS Ornithology. 741967 records from PlutoF platform observations. 47656 records from SPSF - Herbário Dom Bento José Pickel. 76 records from A new species of Fidelia Friese, 1899 (Hymenoptera, Megachilidae), with a key to the species of the genus. 461 records from Guadeloupe_Bananier. 548 records from (Tab. 9.D) Presence and abundance of benthic fauna at station FINO 1 in 2005. 26880 records from KUBI Ornithology Tissue Collection. 7 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 1 records from Nothrus segnis. 2509 records from Type Specimen Database of Museum and Institute of Zoology PAS. 71 records from (Table 5) Selection of Holocene-Pleistocene boundaries in ODP Leg 139 holes. 10137 records from Royal Horticultural Society - RHS lily beetle (Lilioceris lilii) monitoring. 127317 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 55 records from (Table S2a) Nannofossil species richness in the Bass River section. 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 1866 records from Colección de Crustacea del Museo Nacional de Historia Natural de Chile. 2494 records from Marine Environmental Monitoring - Marine Turtles. 1 records from A new species of the genus Sinanapis (Araneae: Anapidae) from Lam Dong province, southern Vietnam.. 4738 records from (Table 3) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-845A. 25530 records from (Table 1) Distribution of planktonic foraminifera in ODP Site 130-806. 934424 records from Fishbase. 4689 records from Funed-Pol - Coleção de lâminas de grãos de pólen. 5194 records from SMNS Palaeontological collection - Amber and fossil insects. 239 records from Irish Federation of Sea Anglers Catch Data. 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 1 records from Oribates gilvipes. 46652 records from SPF - Herbário da Universidade de São Paulo. 28 records from (Table 2) Oligocene to Pliocene nannofossil range chart for ODP Hole 134-828A. 1 records from Hoplophora ferruginea. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 1174 records from PReCAST Marine Mammal Sightings. 225 records from (Table T2) Calcareous nannofossil stratigraphy of ODP Hole 198-1207B. 6237 records from Plecoptera. 234 records from (Table T4) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1211B, Shatsky Rise, Pacific Ocean. 1124142 records from PRECIS. 1219 records from Dutch Butterfly Monitoring Indexes. 190 records from Inventaire National du Patrimoine Naturel : Observations d'hippocampes et syngnathes de France métropolitaine: Programme Hippo-ATLAS. 33070 records from CSIRO Ichthyology provider for OZCAM. 239 records from Systematic review of the neotropical shovelnose catfish genus Sorubim Cuvier (Siluriformes: Pimelodidae).. 49 records from (Table 8) Pliocene to Pleistocene nannofossil range chart for ODP Hole 134-833B. 1 records from Celaeno obsoleta. 13094 records from Mammalia Collection of Institute of Systematics and Evolution of Animals. 28383 records from Notes from the Mycology Herbarium, Oslo (O). 1678 records from Colección de aves del Museo de Historia Natural de la Pontificia Universidad Javeriana. 59799 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 22 records from Colección Parasitológica del Centro Nacional Patagónico (CNP-PAR). 389 records from Amphibian and Reptilian (KIEE-AR). 94696 records from Dutch Centre For Field Ornithology (SOVON) - Breeding Bird Monitoring Program. 2 records from Scaphisoma poussereaui sp. nov. from La Réunion (Coleoptera: Staphylinidae: Scaphidiinae), arange extension of the S. tricolor species group. 544 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 8585 records from RSPB - Bird Conservation Targeting Project (BCTP) in the UK, archived data (2001-2008) - sensitive records. 9216 records from Inventaire National du Patrimoine Naturel : Crustacés Décapodes de France. 1201 records from monocotyledonous_geophytes_of_fergana_valley. 2 records from Simpsonichthys radiosus sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the upper Rio Tocantins basin, central Brazil.. 6 records from Histoire naturelle des Hymenopteres. Deuxieme partie: Les Formicides.. 3 records from Fossil occurrence of calcareous nannofossils from IODP Hole 319-C0009A. 2498 records from (Table T1) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1168A sediments. 1 records from Review of the ant genus Nesomyrmex (Hymenoptera: Formicidae: Myrmicinae) in southern Africa.. 2338 records from Glasgow Museums BRC - Mammal records for Clyde Faunal Area, 1850 to 2007. 5416 records from HUCO - Herbário da Universidade Estadual do Centro-Oeste. 7693 records from NHM, Heteroptera. 23836 records from bird. 26 records from A new species of the Asian schilbid catfish genus Clupisoma from Myanmar, with a redescription of Clupisoma prateri Hora (Osteichthyes: Siluriformes: Schilbidae).. 965 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Oxfordshire Fen Survey 1983 (as held by Thames Valley Environmental Records Centre). 16 records from Taxonomic review of the genus Wasmannia.. 64 records from (Table 2) Planktonic foraminifera species found in sediment trap samples and bottom sediments at Station Vy20-3178. 24 records from (Table 1) Stage of the lemming cycle and nesting parameters of the greater snow geese between 1996-2005, Bylot Island. 190 records from Relative abundance of ostracods in sediment core Sv09. 9 records from (Appendix B) Relative abundance of benthic foraminifera morphotypes in ODP Hole 138-844C. 116995 records from Occurrence records of southern African aquatic biodiversity. 185 records from Macrozoobenthos abundance of the intertidal zone of a sandy beach at the Island Algodoal-Maiandeua, Pará, Brazil. 559 records from (Table 2) Planktonic foraminifera community at DSDP Hole 94-610. 829 records from Devon Biodiversity Records Centre - Dartmoor National Park survey data (1910-1970). 292 records from Gymnotus ucamara: a new species of Neotropical electric fish from the Peruvian Amazon (Ostariophysi: Gymnotidae), with notes on ecology and electric organ discharges.. 31 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto39-47. 25 records from Hyolithen - SMF. 145959 records from SLU Aqua Institute of Coastal Research Database for Coastal Fish - KUL. 32 records from (Table T1) Dinoflagellate cyst and spore/pollen yield and preservation in ODP Leg 188 sites. 8 records from A new species of the genus Nothobranchius (Cyprinodontiformes: Nothobranchiidae) from the coastal area of northeastern Mozambique.. 66722 records from SANT herbarium vascular plants collection. 2731 records from Collection du Musée d'Histoire Naturelle de Nice. 12434 records from Museu Paraense Emilio Goeldi - Coleoptera Collection. 216 records from (Table A2) Stratigraphic distribution of major planktic foraminifer species of ODP Hole 198-1210A. 4766 records from Paläontologie Marburg. 5793 records from Orthoptera collection (EO) of the Muséum national d'Histoire naturelle (MNHN - Paris). 163199 records from Plant Specimen in Yunnan, China from Herbarium (PE),Institute of Botany, Chinese Academy of Sciences. 17618 records from BioGIS - Mammals - INPA database. 5 records from (Figure 8) Relative abundance of nannoliths at DSDP Hole 62-464. 66 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Haematopodidae. 3 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 262155 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 5771 records from Segunda caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 6 records from Collection Myriapoda - SNSD. 9349 records from Harriet Irving Botanical Gardens (HIBG). 1 records from Miriapodi di alcune grotte della Campania. 177239 records from Inventaire National du Patrimoine Naturel : Données ONEMA sur les poissons et écrevisses d'eau douce.. 2560 records from (Table T2) Planktonic foraminifera stratigraphy of ODP Hole 198-1211C sediments. 2402 records from Census of plant species in Bonou forest reserve (Southern Benin). 15 records from Projeto Abrace o Boto Cinza. 2322 records from (Table AT8) Planktonic foraminiferal stratigraphy of ODP Hole 182-1134A. 12 records from New records of Trichoceridae (Diptera) from the island of Mallorca ​. 10606 records from Cercle des mycologues de Montréal Fungarium (CMMF). 384 records from (Supplement Table) Individual body mass, flipper length, oxidative balance indices and telomere length of king penguin chicks (Aptenodytes patagonicus) at the beginning of the post-winter growth. 163 records from (Table 11) Relative frequencies of planktonic foraminifers and cluster arrangement of ODP Holes 127-794A and 127-197B. 2 records from Beiträge zur Kenntnis bulgarischen Chilopoden. Teil V. Das Genus Polybothrus. 116 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Troglodytidae. 166781 records from KUBI Mammalogy Collection. 959 records from RSPB - Black-throated diver national surveys in Scotland (SCARABBS). 8 records from New species of the catfish genus Trichomycterus (Siluriformes, Trichomycteridae) from the headwaters of the rio São Francisco basin, Brazil.. 18521 records from Species plots from the Norwegian Vegetation Mapping Programme. 105 records from People's Trust for Endangered Species - Noble Chafer: Pre-BAP records prior to 1998. 124 records from (Appendix A1) Cenomanian benthic foraminifera of ODP Hole 207-1258A. 146 records from Checklist of aquatic and marshy Monocotyledons from the Araguaia River basin, Brazilian Cerrado. 9 records from Kryptopterus platypogon, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 47499 records from Sphaeroceridae Collection. 218 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2000-2004. Part 2. 2 records from Note sur les fourmis du Musée Zoologique de l'Académie Impériale des Sciences à St. Pétersbourg.. 1210 records from Abundance of megabenthic species in trawl catches per station in addition to table 2 during POLARSTERN cruise ARK-VIII/2 (EPOS). 1 records from Estudio de los frutos y semillas del género Chenopodium en la Argentina. 530 records from Collection Crustacea - KAUMM. 782 records from Lowland lakeshore vegetation in Nord-Trøndelag, Norway. 246 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2005-2006. Part 3. 2 records from The Persian / Arabian Gulf's sole great white shark Carcharodon carcharias (Lamniformes: Lamnidae) record from Kuwait: misidentification of a sandtiger shark Carcharias taurus (Lamniformes: Odontaspididae).. 13403 records from The Herpetology Collection at the Staatliches Museum für Naturkunde Stuttgart. 2513 records from Carabidae of the Tatra Mts.. 3535 records from Colección de Entomología Médica del Instituto Colombiano de Medicina Tropical. 4447 records from Lepidoptera (Observations). 367 records from Clyde River Foundation - Twaite Shad (Alosa fallax) distribution for Scotland, historical to present. 8 records from Pomacentrus aurifrons, a new species of damselfish (Pomacentridae) from Melanesia.. 12808 records from WIWO (NL) - Migration of Pacific Golden Plovers through North-Eastern Mongolia. 1715 records from (Appendix) Planktonic foraminifera abundances in ODP Site 138-847B. 372 records from Colección de Entomología - Arthropoda. 702 records from HSU Vertebrate Museum Reptile Collection. 10 records from A new Neoplatyura Malloch from Finland (Diptera, Keroplatidae). 1 records from Chilopoden und Diplopoden aus Jugoslavischen Hoehlen. 9396 records from RSPB - White-tailed eagle reintroduction in Scotland - Sightings data (RSPB/SNH). 3182 records from Finnish Entomological Database: Heteroptera. 7509 records from Perot Museum of Nature and Science. 1 records from Revision der Ceratozetidae, 5. Ceratozetes thienemanni WILLMANN (Arach., Acari, Oribatei). 55 records from (Table 3) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-840B. 9216 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Diptera_Tipulidae_NL. 1706 records from University of Amsterdam (NL) - Páramo pollen reference collection. 188781 records from Reptiles and Amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from new species of the fungus-farming ant genus Mycetagroicus Brandao & Mayhe-Nunes A new species of the fungus-farming ant genus Mycetagroicus Brandao Mayhe-Nunes (Hymenoptera, Formicidae, Attini).. 2 records from Apistogramma eremnopyge, a new species of cichlid fish (Teleostei: Cichlidae) from Peru.. 1354 records from (Table 1) Planktonic foraminiferal communities at DSDP Holes 94-609B and 94-609. 7 records from Benthic hard-bottom communities abundance at X-Huinay in 2012. 268 records from mcme_uplb_museum_plant_collection. 45467 records from UFP - Herbário UFP - Geraldo Mariz. 3447 records from Colección de Ornitología - Museo de Ciencias Naturales de La Salle. 444 records from Insect Collection from New Caledonia. 77152 records from Conchological Society of Great Britain & Ireland - Mollusc (marine) data for Great Britain and Ireland. 2212 records from RIVM (NL) - Earthworm Observations in Soil Samples. 12 records from Six new, unusually small ants of the genus Leptomyrmex (Hymenoptera: Formicidae).. 21 records from Molecular phylogeny of Banza (Orthoptera: Tettigoniidae), the endemic katydids of the Hawaiian Archipelago. 531 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 678 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 99463 records from NPL collections. 1490 records from (Appendix) Benthic foraminifera in early Eocene sediments of DSDP Hole 48-401. 10 records from Distribution and habitat of the Laotian Rock Rat Laonastes aenigmamus Jenkins, Kilpatrick, Robinson & Timmins, 2005 (Rodentia: Diatomyidae) in Vietnam. 52 records from New data on the jumping spiders of the subfamily Spartaeinae (Araneae: Salticidae) from Africa. 2011 records from Local BioBlitz Challenge 2013. 409 records from Iberian Peninsula and Balearic Island Bathynellacea (Crustacea, Syncarida) database. 61 records from Registros restauración ecológica- Magdalena medio. 8 records from Three new species of seasonal killifishes of the Simpsonichthys antenori species group (Teleostei: Cyprinodontiformes: Rivulidae) from the rio São Francisco basin, Brazil.. 11518 records from Merseyside BioBank - North Merseyside Insects (verified). 77 records from Empria and Monsoma in Japan. 140 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 38 records from The Oriental species of the ant genus Probolomyrmex (Insecta: Hymenoptera: Formicidae: Proceratiinae).. 5 records from Oribatid mites from Switzerland, IV (Acari: Oribatida: Suctobelbidae). 654 records from Helgeland Museum, Tabanidae. 612934 records from Waarnemingen.be - Butterfly occurrences in Flanders and the Brussels Capital Region, Belgium. 99 records from French national collection of Solanum tuberosum. 57306 records from Colección Herbario Federico Medem Bogotá - FMB. 2608 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 7 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Melanopareiidae. 23 records from (Table 2) Live (stained) benthic foraminifera from stations in the northern Gulf of California. 73975 records from Palaeozooloical Collections (PZ), Swedish Museum of Natural History (NRM). 4844 records from SJRP-Bryophyta - Herbário de Bryophyta de São José do Rio Preto. 900522 records from FLORIVON. 111802 records from Highland Biological Recording Group - HBRG Insects Dataset. 94709 records from Merseyside BioBank - North Merseyside Flowering Plants (unverified). 51969 records from Palaeobiology - Vertebrate Fossils Collection - Non Mammalia - Royal Ontario Museum. 387501 records from Species data extracted from the National Vegetation Database. 68 records from (Table 8) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-851B. 660 records from VMNH Invertebrate Paleontology. 1 records from Beitrag zur Kenntnis der Höhlen-Oribatiden der Schweiz (Acari: Oribatida) (Neue und interessante Milben aus dem Genfer Museum LI). 2090 records from Crustáceos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CERBMcr-UV). 2247562 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 19127 records from Biological Records Centre - Cerambycidae Dataset. 26835 records from Herbario Pontificia Universidad Javeriana. 12 records from (Table 1) Length, weight, fat content and age of Norwegian spring spawning herring (Clupea harengus) during 2007. 14 records from Inventario Herpetológico Pauto J, Rincón del Soldado, Yopal, Casanare. 26 records from A new species of Chondrostoma Agassiz, 1832 (Cypriniformes: Cyprinidae) with sexual dimorphism from the lower Rio Tejo Basin, Portugal.. 68304 records from IICT Herbário LISC. 85003 records from Herbario Universidad de Antioquia (HUA). 36974 records from Environment Agency - Environment Agency Rare and Protected Species records v1. 358 records from (Appendix D) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Site 161-975. 634257 records from Inventario Español de Especies Terrestres (MAGRAMA). 751 records from Trichoptera (caddisflies) of Ireland. 30 records from Lacantunia enigmatica (Teleostei: Siluriformes) a new and phylogenetically puzzling freshwater fish from Mesoamerica.. 1481 records from Reptilia notes, NTNU, Trondheim. 34502 records from Merseyside BioBank - North Merseyside Birds (verified). 198 records from Segunda caracterización biológica de hormigas cazadoras del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 1 records from On the morphology, biometry and biogeography of Lamtopyxis callistoma ( Amoebozoa : Arcellinida ). 318 records from A taxonomic review of the genus Azteca (Hymenoptera: Formicidae) in Costa Rica and a global revision of the aurita group.. 618 records from RSPB - Scottish Crossbill National Survey in the UK in 2008 (SCARABBS). 1329 records from API_CRSN_Data. 7671 records from HERBAM - Herbário da Amazônia Meridional. 5116 records from Caracterización de la avifauna de las cuencas de los Ríos Cañas (Dibulla–Guajira), Garupal (Valledupar–Cesar), Arroyo Grande (San Juan de Nepomuceno–Bolívar), Aipe (Huila), Yaví (Tolima), Dagua (Valle del Cauca) como insumo para la identificación de oportunidades de conservación y de recuperación de servicios ecosistémicos del bosque seco.. 2 records from Adetomyrma, an enigmatic new ant genus from Madagascar (Hymenoptera: Formicidae), and its implications for ant phylogeny.. 2174 records from MLZ Mammal Collection (Arctos). 110783 records from ICN - Herbário do Instituto de Ciências Naturais. 50317 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 225 records from Meiobenthos of target sites of Crimea in 2009/2010. 20 records from (Table 2) Counts of live (stained) benthic foraminifera from stations in the northern Gulf of California. 19 records from Record of 7 acritarch taxa from the Miocene, Pliocene and Pleistocene of ODP Hole 151-910C. 4490 records from Colección Herpetológica del Museo Nacional de Historia Natural de Chile. 93 records from (Table 5) Oligocene to Pleistocene nannofossil range chart for ODP Hole 134-829A. 157566 records from Lund Museum of Zoology - Insect collections (MZLU). 88771 records from URM - Herbário Pe. Camille Torrand. 6258 records from Invasive species - Chinese mitten crab (Eriocheir sinensis) in Flanders, Belgium. 28 records from RSPB - Black grouse lek survey in Moray and Nairn 2009 (RSPB). 40 records from Inventario de Herpetología en el Área Sujeta a Acuerdos de Conservación Voluntaria Quebrada Aguazula, Rincón del Soldado, Yopal. 601 records from Dinoflagellate cyst species of sediment core GeoB10732-3. 1 records from On centipedes (Chilopoda) of Albania, 2. 75639 records from University of Alberta Vascular Plant Herbarium (ALTA). 3 records from Note su alcune specie di chilopodi della regione palestinese. 807 records from National Trust for Scotland - NTS Properties Sensitive Species Records 1800-2013. 1 records from Myriopoden von Kreta, nebst Bitraegen zur allgemeinen Kenntnis einger Gattungen. 3 records from On two Italian Lithobius species described by Silvestri, with taxonomic notes on the genus Eupolybothrus Verhoeff (Chilopoda, Lithobiida). 652 records from Spider species diversity from wet and dry habitats. 4501 records from Colección de Mamíferos del Centro Nacional Patagónico. 1 records from Hoplophora decumana. 103310 records from Plant Specimen from Herbarium (CDBI) in China, Chengdu Institute of Botany, Chinese Academy of Sciences. 24 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 90 records from Taxonomy of the plesiolebiasine killifish genera Pituna, Plesiolebias and Maratecoara (Teleostei: Cyprinodontiformes: Rivulidae), with descriptions of nine new species.. 44 records from Solanum_baretiae. 7479 records from BioGIS - Vascular plants - Israeli Gene Bank. 367 records from Longhorn and buprestid beetles (Coleoptera: Cerambycidae, Buprestidae) of the forest-steppe “Bielinek” reserve and its surroundings. 1 records from Zooplankton abundance measured on water bottle samples during Jan Mayen cruise JM7. 73 records from (Table 7) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-850B. 1 records from Oribates flammula. 24 records from New distributional data on ascidian fauna (Tunicata: Ascidiacea) from Mandapam coast, Gulf of Mannar, India. 57401 records from Naturalis Biodiversity Center (NL) - Mammalia. 6 records from (Table 3) Middle Eocene silicoflagellates from DSDP Hole 95-613. 24 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2003. 412 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001E. 3779762 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 179 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cuculidae. 51181 records from VIS - Fishes in estuarine waters in Flanders, Belgium. 10620 records from CSIRO, SRFME, Algal Biomass, Perth region, Southwest Australia, 2003-2005. 956 records from Colección de reptiles del Museo de Historia Natural de la Pontificia Universidad Javeriana. 10 records from Eupolybothrus cavernicolus Komerički & Stoev sp. n. (Chilopoda: Lithobiomorpha: Lithobiidae): the first eukaryotic species description combining transcriptomic, DNA barcoding and micro-CT imaging data. 6855 records from Echinoderm collection of National Museum of Nature and Science. 1 records from Oribates picipes. 202 records from BTCV Scotland - BTCV wildlife counts recording workshops. 16826 records from Tachinid Recording Scheme - Tachinid Recording Scheme - GB and Ireland records. 374 records from published_chenopodium_vulvaria_observations. 7403 records from Freshwater fishes of Hidalgo state (Mexico) in the MZNA fish collection of the University of Navarra (Spain). 18 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001I. 5850 records from UAFMC Fish. 1 records from Taenioides kentalleni, a new species of eel goby from Saudi Arabia (Gobiidae: Amblyopinae).. 77 records from Xiphosura collection of National Museum of Nature and Science. 365 records from Colección Herpetológica de la Patagonia. 1 records from A record of Anzygina billi Fletcher & Larivière, 2009 (Hemiptera: Cicadellidae) from New Zealand. 2082 records from Vietnam Type Culture Collection. 4 records from First verified record of the ant genus Calyptomyrmex (Hymenoptera: Formicidae) from India, along with a revised key to known Indomalayan species. 4 records from A third species in the rare Australian ant genus Peronomyrmex Viehmeyer (Hymenoptera: Formicidae).. 1 records from Eremaeus hepaticus. 6817 records from Colección de Reptiles del Instituto Alexander von Humboldt. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 13993 records from Herpetology. 110660 records from The avian collection at the Natural History Museum, Oslo, Norway. 146 records from A taxonomic revision of the catshark genus Poroderma Smith, 1837 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 798 records from Pauropoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 2 records from On the female of Gypona reversa DeLong & Martinson, 1972, with emphasis on genital structures (Insecta: Hemiptera: Cicadellidae). 663 records from Colección de Aves Museo Universitario de la Universidad de Antioquia. 1 records from Pelops torulosus. 9 records from Inventario Herpetológico Pauto M, La Primavera, Yopal, Casanare. 173415 records from Hymenoptera specimen database of Kyushu University. 1 records from Arthropoden aus südostalpinen Höhlen.. 1 records from Dolistenus menozzii n. sp. della famiglia Platydesmidae (Miriapodi Colobognati); e altri miriapodi della Calabria. 106 records from (Appendix II) Foraminifera abundance in DSDP Hole 22-214. 13086 records from Collection of Coleoptera. 52 records from Isotope tracer experiment: meiofauna counts. 26847 records from Merseyside BioBank - North Merseyside Other Taxa (unverified). 1722 records from Cambridgeshire & Peterborough Biological Records Centre - Orthoptera dataset held by CPERC. 20416 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 3257 records from fundiv france database. 61981 records from Stuart M. Fullerton Collection of Arthropods (UCFC), University of Central Florida. 76 records from (Fig. 2) Vertical density profiles of meiofauna taxa in surface sediments of Potter Cove, King George Island, Antarctic Peninsula. 2392 records from Fongs d'Andorra. 60710 records from Leicestershire and Rutland Environmental Records Centre - Leicestershire & Rutland Coleoptera. 781 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2011. 1004 records from National Museum of Marine Biology and Aquarium. 1197 records from North Atlantic (Rockall Plateau) coccolith assemblage data for MIS 5 of ODP Hole 162-980B. 4373 records from Colección del Herbario de la Universidad Tecnológica del Chocó. 4944 records from Inventaire National du Patrimoine Naturel : Flore de l'Ain. 1 records from Cepheus latus. 69797 records from Lepidoptera collection, Natural History Museum, University of Oslo. 255 records from Inventario de Plantas Mámbita. 253105 records from Lyman Entomological Museum (LEMQ). 17802 records from The Bat Conservation Trust - Colony Count Survey. 39 records from University Marine Biological Station Millport - 1995 EC Study Contract Clyde Sea Nephrops Stock Assessment Study. 9054 records from The Scottish Ornithologists' Club - Highland bird data 2002 - 2003 - non-breeding records. 4 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2012. 7873 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Himalayan Balsam Surveys (WT) - 2010-2012. 4266 records from UAFMC Birds. 36 records from New ants (Hymenoptera: Formicidae) from Micronesia.. 1349 records from Caracterización florística y estructura de los relictos de bosque seco tropical en el bajo Cauca, jurisdicción Corantioquia. 5053399 records from Southern African Bird Atlas Project. 63 records from (Data S1) Palynology of ODP Site 119-739. 259 records from (Table 7) Benthic foraminifera genera assemblage at DSDP Section 80-548A-22. 96 records from (Table T4) Biogenic and mineral composition of sediments cored in Hamburg-Langenhorn. 585 records from Ascomycetes of Russian Fennoscandia. 5 records from Ventichthys biospeedoi n. gen. et sp. (Teleostei, Ophidiidae) from a hydrothermal vent in the South East Pacific.. 16749 records from IMOS - AusCPR: Phytoplankton Abundance. 26152 records from Herts Bird Club - Hertfordshire Breeding Bird Atlas : 1967-1973. 119366 records from The digitization of plant specimens of NTU. 456 records from Levantamento de Arbóreas do Parque Nacional do Jaú. 8164 records from Mamíferos de la colección del Instituto Alexander von Humboldt. 130059 records from Inventaire National du Patrimoine Naturel : Mammifères de France. 80128 records from NCSM Fishes Collection. 8880 records from Actualisation de la cartographie des Ptéridophytes de France et d'Europe occidentale. 5 records from Chromosome studies in the aquatic monocots of Myanmar: A brief review with additional records. 918 records from Western Australia Museum, Crustacea Specimens, Ningaloo Reef - Northwest Cape, Northwest Australia, 1920-2004. 62099 records from Marine Biological Association - DASSH Data Archive Centre Academic surveys. 51900 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 455 records from (Table T2) Calcareous nannofossil abundance across the Oligocene/Miocene boundary of ODP Hole 189-1168A sediments. 63 records from Polypterus mokelembembe, a new species of bichir from the central Congo River basin (Actinopterygii: Cladistia: Polypteridae).. 2848 records from Kangawalla Bird Sightings. 1371 records from (Table T2) Abundance of dinoflagellates and other palynomorphs in Eocene-Oligocene sediments from ODP Hole 189-1172A. 24855 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 38 records from Fourteen new species of Pseudisobrachium (Hymenoptera, Bethylidae) from Atlantic rain forest of Espírito Santo, Brazil.. 2576 records from Hosted Invertebrate Collection 01. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 41 records from Studies on the Zoarcidae of the southern hemisphere. X. New records from western Antarctica.. 4857 records from University of Alberta Museums, Entomology Collection. 17 records from Bridging the distributional gap of Tylorida striata (Thorell, 1877) and new synonymy (Araneae: Tetragnathidae). 91 records from Zooplancton de sistemas acuáticos artificiales y naturales de Colombia. 1 records from Pollen analysis of sediment profile KAIX_A from Kaiserwinkel. 4 records from (Table 3) Mean plasma lipid content, and plasma PCB and OH-PCB concentration of polar bear (Ursus maritimus) mothers and cubs. 26 records from A revision of the western hemisphere Chalcoscirtus (Araneae: Salticidae). 552 records from (Table 2) Relaticve abundances of Eocene to Oligocene planktonic foraminifera in ODP Hole 135-841B. 31 records from Alobevania, a new genus of neotropical ensign wasps (Hymenoptera: Evaniidae), with three new species: integrating taxonomy with the World Wide Web.. 1643239 records from SA Flora (BDBSA). 9173 records from Colección de líquenes del Herbario "Jaime Andrés Rodríguez". LEB-Lichen. 360 records from (Figure 1g) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3174. 19 records from (Table 1) Abundance of unicellular eukaryotes in ice cores collected during the July 2008 CCGS Amundsen cruise in Darnley Bay. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 31 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 1998. 86556 records from NINA Vanndata øvrige arter. 200 records from (Table T1) Neogene stratigraphy of diatoms, ebridians and endoskeletal dinoflagellates in ODP Hole 183-1138A. 1323 records from (Table 10) Benthic foraminifera in late Miocene sediments of DSDP Hole 90-591. 745 records from (Table 2) Benthic foraminifers at DSDP Hole 72-518. 223433 records from Phytochorologie des départements français. 45 records from Scottish Natural Heritage - Surveys of Najas flexilis (Slender naiad) in Scotland 2004 â 2011. 4498 records from Colección Herbario Universidad Católica de Oriente. 32 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 50 records from (Table 1) Biometrics of five seabird species from Kongsfjorden, Svalbard. 964 records from Arachnida del Museo de Entomología de la Universidad del Valle. 724 records from Scorpiones collection (RS) of the Muséum national d'Histoire naturelle (MNHN - Paris). 373 records from Dinocyst occurrences and zonations from IODP Hole 313-M0029A. 216 records from (Table T1) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1135A. 32 records from Archaea Collection in BCRC. 2 records from Arthropoden aus südostalpinen Höhlen.. 41 records from Altholzparzelle Eilenriede Hannover. 1 records from A new Garcorops species from Madagascar copal (Araneae: Selenopidae). 175 records from (Table 6) Benthic foraminifera genera assemblage at DSDP Section 80-548A-16-3. 1 records from Erysipelothrix inopinata sp. nov., isolated in the course of sterile filtration of vegetable peptone broth, and description of Erysipelotrichaceae fam. nov.. 71 records from RSPB - Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010.. 18 records from First report of Dicopus longipes (Subba Rao) (Hymenoptera: Chalcidoidea) from India with new distribution data on some species. 60344 records from AM: Freshwater Invertebrates (1900-2005). 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 4641 records from Hymenoptera collection (EY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 26 records from Myoglanis aspredinoides (Siluriformes: Heptapteridae), a new catfish from the Río Ventuari, Venezuela.. 1627 records from RSPB - Bird survey records from RSPB's London House Sparrow Parks Project 2009-2010, covering 19 London parks and surrounding streets (Funded by SITA Trust,. 12512 records from ULg_Hexapoda. 841 records from Dorset Environmental Records Centre - Dorset Invasive Alien Plants - NBN South West Pilot Project Case Studies. 11 records from Pollen profile from sediment core AV14_K2-4. 10 records from Devon Biodiversity Records Centre - Devon giant hogweed data 1997 to 2000. 5872 records from EcoRecord - Beetle (Coleoptera) Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 46 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 2394 records from Colección Científica de Referencia Zoológica del Chocó- Herpetología. 4761 records from SMDB - Santa Maria Departamento de Biologia. 5368 records from Dutch Mammal Society (NL) - Mammal observations extracted from historic reports. 33522 records from Dragonfly Ireland. 4286 records from Inventaire National du Patrimoine Naturel : Atlas de la flore de Lorraine. 303 records from The South American annual killifish genus Austrolebias (Teleostei: Cyprinodontiformes: Rivulidae): phylogenetic relationships, descriptive morphology and taxonomic revision.. 56 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Alcedinidae. 2880 records from Coleoptera, NEF. 2297 records from Joint Nature Conservation Committee - England Otter Survey Database. 1408 records from (Table 2) Distribution of Campanian-Maestrichtian agglutinated foraminifers in DSDP Hole 78-543A. 2782 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Taminango, Nariño. 471 records from Aschelminth collection of National Museum of Nature and Science. 496 records from Colección Entomológica del Centro Nacional Patagónico “Francisco P. Moreno” (CNP-CE). 766 records from Antarctic Porifera database from the Spanish benthic expeditions: Bentart, Gebrap and Ciemar. 2 records from Ituglanis paraguassuensis sp. n. (Teleostei: Siluriformes: Trichomycteridae): a new catfish from the rio Paraguacu, northeastern Brazil.. 918 records from Caracterizaciones rápidas de biodiversidad en grupos biológicos de la planicie del valle del río Cauca. 367341 records from University of Florida Vertebrate Paleontology. 12051 records from ISM Ornithology Collection. 6 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 11 records from (Table AT2) Petrology in point counts of ODP Hole 210-1276A, two ODP Leg 173 sites and DSDP Hole 47-398D. 98423 records from Insect species recorded in sugarcane fields of Khon Kaen Province, Thailand, over three seasons in 2012. 26624 records from Monitoring data from the federal state Bavaria (Germany). 7 records from First record of the male of the widespread Calliscelio elegans (Perkins) (Hymenoptera, Platygastridae) along with some taxonomic notes on the species. 808 records from Greater Manchester Ecology Unit - Distribution of Great Crested Newts in Greater Manchester. 53050 records from CESJ - Herbário Leopoldo Krieger. 380 records from (Table 4) Benthic foraminiferal genera in DSDP Core 95-612-16 and 95-612-17. 21 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rynchopidae. 25813 records from Amphibian Specimens. 218609 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 355 records from Culture Collection of Cryophilic Algae. 327 records from (Table 1) Fossil record of foraminifera and ostracoda from Albersdorf clay pit, north Germany. 2 records from Note tassonomiche e faunistiche su Chilopodi della Grecia (Chilopoda). 767 records from BioGIS - Bats - Asaf Tsoar database. 6 records from On a new species of the genus Moenkhausia Eigenmann (Ostariophysi: Characidae).. 27 records from RSPB - Bearded Tit National Survey in Britain 1992 (SCARABBS). 2802 records from Merseyside BioBank - North Merseyside Fish (unverified). 52 records from The Myrmica punctiventris and M. crassirugis species groups in the Nearctic region.. 2 records from A New Species from Mountain Forest Soils in Japan: Porosia paracarinata sp. nov., and Taxonomic Concept of the Genus Porosia Jung, 1942. 2824 records from Fundación Miguel Lillo - Colección Invertebrados. 4 records from First verified record of the ant genus Calyptomyrmex (Hymenoptera: Formicidae) from India, along with a revised key to known Indomalayan species. 3 records from A new species of the Asian catfish genus Pseudolaguvia from Myanmar (Teleostei: Ostariophysi: Siluriformes: Erethistidae).. 9959 records from UAM Fish Collection (Arctos). 44469 records from DMNS Bird Collection (Arctos). 81329 records from natagora-earlybirds. 3688 records from Clare Biological Records Centre dataset. 3945 records from TTRS Ornithology. 582 records from Bioblitz 2013 Copenhagen Denmark. 127876 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 287831 records from Coordinated Waterbird Counts. 1 records from Nothrus pollinosus. 1364 records from Irish Collembola records. 723 records from The Fish Collection at the Zoologische Staatssammlung München. 108 records from Studies in Hawaiian Diptera I: New Distributional Records for Endemic Asteia (Asteiidae). 1131 records from (Table T8) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zone P4. 9879 records from Bibliographic records of Angola mammals. 21704 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Netherlands. 98 records from RSPB - Twite national sample survey in the UK in 1999 (SCARABBS). 857 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 255 records from GENT Lactarius Deliciosi. 1 records from Myriopoden von Epirus. 1049 records from Colección de Crustáceos Decápodos y Estomatópodos del Centro Oceanográfico de Cádiz: CCDE-IEOCD. 2 records from (Supplement Table 3) Percentage cover abundance of plants recorded at the Fell-field Site on Disko Island. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 2448 records from (Table T2) Abundance of stratigraphically important planktonic foraminifera in ODP Hole 186-1151A sediments. 2654 records from Collection of Hymenoptera. 5 records from Specimen records associated with "A troglomorphic spider from Java (Araneae, Ctenidae, Amauropelma). 15 records from (Table 1) Occurrence and abundance of late Early Cretaceous radiolarians at DSDP Hole 62-463. 17 records from (Table A) Fauna associated with Bathymodiolus azoricus mussel beds within the Menez Gwen hydrothermal field, Mid-Atlantic Ridge. 33 records from Relative abundance of Florisphaera profunda in ODP Hole 121-758C. 1 records from Oppiella signata, eine neue Art der Familie Oppiidae aus dem Osterzgebirge (Acari, Oribatei). 6551 records from The Fossil Fish Collection at the Jura-Museum Eichstätt. 3 records from Melampyrum sylvaticum as a pre-diapause host plant of the scarce fritillary (Euphydryas maturna) in Finland. 8 records from (Table 1) Trawled distance, Isopoda per 1000 m haul length, expected number of species, evenness, and the Shannon-Wiener index during POLARSTERN cruise ANT-XIX/3 (ANDEEP I). 39035 records from Merseyside BioBank - North Merseyside Birds (unverified). 397 records from Danish Lacewings (Neuroptera). 176 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2010. 76 records from (Appendix A2) Calcareous nannofossil counts of ODP Site 207-1260. 3 records from Taxonomic considerations on Lobocneme Rehn, 1911 and Paroxyopsis Rehn, 1911 and a new synonymy (Insecta Mantodea: Stagmatopterinae). 189 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Threskiornithidae. 202 records from Uncorrected Mg/Ca and sea surface temperature data for Site 165-1000. 3377 records from USGS ASC - Changing Arctic Ecosystems - Alaska - Birds. 873 records from Kartlegging av spredning av fremmede bartrær. 289 records from (Appendix B) Nannofossil abundance in ODP Hole 165-998A sediments. 76253 records from Irish Vascular Plant Data - Paul Green. 1 records from A new African Apiocera species (Apioceridae, Diptera). 13 records from Taxonomy of European Damaeidae (Acari: Oribatida) III. Species of the Kunstidamaeus tenuipes (Michael, 1885) group, with a description of Kunstidamaeus fraterculus n. sp. from East Slovakia. 4 records from Pollen analysis of sediment profile PLU01 from Plussee. 2475 records from HSU Wildlife Eggs and Nests. 3359932 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 3045 records from ESAS cetacean sightings from 1980 to 2003.. 72236 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 139 records from Nematode abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas ?. 19237 records from Alterra (NL) - Biological Indicator Soil Quality-Microarthropods inventory in different habitats. 207 records from BioAcoustica: Wildlife Sounds Database. 7 records from Calvia explanata sp. n. (Coleoptera: Coccinellidae: Coccinellinae) from the Indian Subcontinent. 240 records from Saproxylic beetles of the Po plain woodlands, Italy. 102 records from Sipuncula collection of National Museum of Nature and Science. 588 records from Relative abundance of ostracods in sediment core Lz1120. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 6083 records from Biological Records Centre - Sepsidae (Diptera) records from Britain and Ireland to 1985. 8 records from (Table 2) Monthly statistics of king penguin (Aptenodytes patagonicus) colony arrivals, Possession Island. 1 records from Nothrus pigerrimus. 9997 records from Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 45 records from Sediment age, abundance of planktonic foraminifera shells, degree of their dissolution, percentage of benthic foraminifera in total foram fauna, Core GC-11, Sea of Okhotsk. 156 records from Schizomida Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 8 records from (Table 3) Characteristics of the Chamelea gallina population on the beach of the Anapa Bay Bar in October 2010. 7432 records from HBRA - Herbário do Instituto de Estudos Costeiros da Universidade Federal do Pará. 5 records from (Table 2) Osmium isotope ratios and Re-Os element content for cleaned and uncleande foraminifera of ODP Hole 121-758A. 1287 records from RAVON (NL) - Fish observations extracted from Hoek (1888) and Hoek (1897). 644 records from (Table T1) Planktonic foraminiferal stratigraphy of ODP Hole 173-1065A sediments. 382 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Scolopacidae. 1581 records from Colección Ornitológica de la Universidad Industrial de Santander. 7410 records from Helgeland Museum, Lepidoptera. 108 records from (Table 5) Live benthic foraminifera in sediment core SO130-236MC. 924 records from (Table 15) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-592. 52 records from CIM Specimens. 1557 records from Hypogean Crustacea recording scheme - Hypogean macro-Crustacea records. 48 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1209A. 90851 records from CUMV Fish Collection (Arctos). 6065 records from LISU Herbario Angola. 3 records from (Table 2) Upper Eocene silicoflagellates from DSDP Hole 95-612. 6 records from Fundulopanchax kamdemi (Cyprinodontiformes: Nothobranchiidae) a new species from Korup National Park, western Cameroon.. 6 records from A new Savignia from Cretan caves (Araneae: Linyphiidae). 351176 records from Plantae of Costa Rica (INBio). 29490 records from Tromsø Museum, Fungi. 1138 records from (Table T2) Benthic foraminfera stratigraphy of ODP Hole 199-1220B sediments. 43 records from (Table 3) Relative abundance of Azolla spp., peridinoid dinocysts, gonyaulacoid dinocysts, non-saccate pollen, bisaccate pollen and spores from the Lomonosov Ridge during different Arctic coring expeditions. 583 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 138-847B. 50 records from Université Pédagogique Nationale de Kinshasa (UPN). Plantes phytosanitaires. - Projet CABIN. 2358 records from MISE Project Otter Records, 2011-2015. 13717 records from OUPR - Herbário "Professor José Badini". 92 records from (Appendix) Diversity indices of benthic foraminiferal fauna of DSDP Hole 48-401. 8 records from Five new species of the damselfish genus Chromis (Perciformes: Labroidei: Pomacentridae) from deep coral reefs in the tropical western Pacific.. 45 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 50 records from A survey of the family Carabodidae C. L. Koch, 1836 (Acari: Oribatida). 895 records from Lichen.ie Data. 968 records from (Table T1) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones Palpha-P3b. 372 records from El efecto de la variación ambiental en la diversificación de anfibios y la prevalencia de su patógeno mortal: Un transecto por los humedales desde el Magdalena Medio hasta la Orinoquía. 2143 records from Lepidoptera collection (EL) of the Muséum national d'Histoire naturelle (MNHN - Paris). 155 records from Megophthalmidia_of_North_America. 7208 records from Royal Horticultural Society - Records from the RHS insect reference collection. 53 records from Royal Horticultural Society - Wisteria scale (Eulecanium excrescens) records acquired by the Royal Horticultural Society. 58 records from Mamíferos laguna El Tinije. 133656 records from NINA insect database. 197 records from Inventaire National du Patrimoine Naturel : CBN Aquitaine-Poitou-Charentes. 1080 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 499 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 30 records from (Table 1) Carbonate constituents and quartz in the sand-sized fraction in Mississippi Fan sediments, DSDP Hole 96-615. 11731 records from HAS-Algae - Coleção Ficológica do HAS. 1 records from Zetes ephippiatus. 34237 records from Colección Nacional de Aracnología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1246 records from (Table 2) Relative abundances of benthic foraminifera in ODP Hole 128-798B. 1 records from Études myrmécologiques en 1886.. 15879 records from HAMAB - Herbário Amapaense. 710 records from Thames Valley Environmental Records Centre - Natural England Bat Records for Berkshire and Oxfordshire (Held by Thames Valley Environmental Records Centre). 1 records from Zetes fuscomaculatus. 22033 records from CUMV Mammal Collection (Arctos). 151 records from Molluscan fauna of Gueishan Island of Taiwan. 68 records from Late Pleistocene planktonic foraminifera of Hole 302-M0004C (Addendum 1). 2 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 568 records from (Appendix 2) Calcareous nannofossils in ODP Hole 189-1172A. 132 records from (Table T2) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1049B. 1470 records from Institut Menorquí d'Estudis. Herbarium Generale Minoricae: HGM. 1894 records from Aves Playeras y Otras Aves Asociadas a Arrozales en los Departamentos de Casanare y Meta en 2009 - 2010. 2 records from Lubbockichthys myersi, a new species of dottyback fish from Guam (Pseudochromidae: Pseudoplesiopinae).. 820552 records from Fauna Atlas N.T.. 1952 records from ISM Ichthyology Collection. 5 records from A new species of Notarius (Siluriformes: Ariidae) from the Colombian Pacific.. 260 records from SuLaMa reptile survey II 2012. 4779 records from (Table S1) Benthic foraminifera of ODP Holes 199-1218A and 199-1219A. 479 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 93276 records from Merseyside BioBank - North Merseyside Flowering Plants (verified). 47 records from Three new Parananochromis species (Teleostei, Cichlidae) from Gabon and Cameroon, Central Africa.. 2476 records from EcoRecord - Bug (Hemiptera) Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 12 records from (Table 1) Sex, age and numbers of polar bear skulls (Ursus maritimus) collected in Svalbard. 301 records from Revision of Archaeoteleia Masner (Hymenoptera: Platygastroidea, Scelionidae).. 153 records from National Pine Marten Survey of Ireland 2005 - 2007. 19 records from Counts of benthos communities in Kongsfjorden in 2009. 31000 records from Plant Specimen Database of Tama Forest Science Garden, Forestry and Forest Products Research Institute, Japan. 6 records from MfN - Micropaleontology. 12 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 1996. 1 records from Die vom k. k. Oberartze Herrn Dr. Justyn Karlinski im Jahre 1887 in Bosnien, der Herzegowina und in Novibazar gesammelten Myriopoden. 3904981 records from FlorKart - FlorenKartierung Gefaesspflanzen. 496530 records from Field Museum of Natural History (Zoology) Bird Collection. 109 records from A taxonomic revision of the genus Oxyopomyrmex André, 1881 (Hymenoptera: Formicidae). 12109 records from Inventario de fauna presente en la jurisdicción de Corantioquia. 11 records from A new species of Hemigrammus Gill, 1858 (Characiformes: Characidae) from Rio Caura, Venezuela.. 3 records from A new species of Lyssomanes Hentz, 1845 from Brazil (Araneae: Salticidae). 149 records from (Appendix A) Palynofacies raw counts of DSDP Hole 38-338. 69 records from (Table 11) Distribution of coccoliths along Core AMK7-786 from the Tajura Rift. 1948 records from CCBER Mammalogy Collection. 92 records from Bothrocara nyx: a new species of eelpout (Perciformes: Zoarcidae) from the Bering Sea.. 1 records from Pollen analysis of sediment profile BIB00 from Biber See. 136 records from Plants galls. 31 records from The identity of catfishes identified as Mystus cavasius (Hamilton, 1822) (Teleostei: Bagridae), with a description of a new species from Myanmar.. 41630940 records from Artdata. 464 records from Lepidoptera collection, NTNU, Trondheim. 948 records from Field Study Group of the Dutch Mammal Society (NL) - 2008 - Mammal Survey Muntii Padurea Craiului - Apuseni mountains, Romania. 4 records from Beiträge zur Kenntnis der Spinnenfauna des Kt. Tessin III - Für die Schweiz neue und bemerkenswerte Spinnen (Arachnida: Araneae). 132 records from (Table 1) Relative abundances of benthic foraminifera in ODP Site 128-798C. 9123 records from Flora of Słowiński National Park, Poland. 1698 records from RSPB - Red-throated diver national surveys in Scotland - raw data (SCARABBS). 7551636 records from BirdLife Australia, Birdata. 15597 records from Countryside Council for Wales - Skomer Marine Nature Reserve (MNR) Marine Monitoring Programme. 540 records from Countryside Council for Wales - CCW Freshwater Fish ad hoc Records for Article 17 Reporting. 2 records from Simpsonichthys suzarti sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual fish from the Rio Pardo floodplains, northeastern Brazil.. 9 records from Cypridinid Ostracods. 20 records from Inventario Herpetológico EPF Floreña, Yopal, Casanare. 558 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 99830 records from Swedish Malaise Trap Project (SMTP) Collection Inventory. 1095 records from (Figure 3) Distribution of dinoflagellate cysts in the late Albian of DSDP Hole 79-547B. 2577 records from Shellfish (WSHN-MS). 519292 records from Museum Victoria provider for OZCAM. 21590 records from Butterflies of Ireland. 4 records from New genus of diminutive microhylid frogs from Papua New Guinea. 540 records from Streamlining the use of BOLD specimen data to record species distributions: a case study with ten Nearctic species of Microgastrinae (Hymenoptera: Braconidae). 71 records from (Data S1) Palynology of ODP Site 113-696. 1 records from Nouveautes sur la faune des Chilopodes de Yougoslavie. 10 records from New records of Microgaster deductor Nixon, 1968 (Hymenoptera: Braconidae: Microgastrinae) for the Holarctic region, with comments on its historical distribution. 314 records from Peces laguna El Tinije. 252 records from RSPB - Black grouse leks in the Forest of Clunie, 2002-2010 (RSPB, SNH). 1905 records from BioGIS - Reptiles - INPA database. 11 records from (Figure 4) Distribution of late Paleocene calcareous nannofossils in ODP Hole 132-810C. 75 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 16621 records from Crustacea collection of National Museum of Nature and Science. 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 13325 records from Herbier du Bénin. 90 records from University of Amsterdam (NL) - Páramo Vegetation Research, paramo in the Sabana de Bogota area, Colombia. 541 records from (Table T6) Biostratigraphy of important benthic foraminifer taxa in sediments cored in Ratekau, Schleswig-Holstein. 1612 records from (Figure 8b) Distribution of Cretaceous planktonic foraminifers, calpellionids and associated organisms from DSDP Hole 77-535. 18940 records from Cowan Tetrapod Collection - Mammals. 1803 records from Flora of tanzania. 11729 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Hymenoptera_Bombidae_Types. 51748 records from Museu Paraense Emilio Goeldi - ichthyology Collection. 26 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 4 records from (Figure 10) Relative abundance of nannoliths at DSDP Hole 62-466. 906 records from Digital Florula - Las Cruces Biological Station. 27988 records from Inventaire National du Patrimoine Naturel : Loup en France. 107 records from (Appendix 3) Calcareous nannofossils in ODP Hole 113-690B. 2957 records from HSU Wildlife Mammals. 695 records from (Table 5) Benthic foraminiferal community at DSDP Site 94-610. 370 records from Ichthyologie ZMK. 657 records from MVZ Hildebrand Collection (Arctos). 159024 records from Lund Museum of Zoology (MZLU). 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 1 records from Protozoa ZMK. 450 records from Sea surface temperature and salinity reconstructions for sediment core LaPAS-KF02. 1004 records from Aix-Marseille Université - MARS herbarium – Cytogenetic data-base. 77244 records from Mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 711 records from Odonata collection, NTNU, Trondheim. 2444 records from Colección de Algas del Herbario Nacional, Museo Nacional de Historia Natural de Chile. 246 records from (Table 2) Distribution of Cretaceous nannofossils at DSDP Hole 79-545. 3 records from A revision of the Neotropical spider genus Ancylometes Bertkau (Araneae: Pisauridae). 127226 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 27 records from Lioscorpius trifasciatus, a new scorpionfish (Scorpaeniformes: Setarchidae) from the South-West Pacific Ocean.. 38282 records from CSIRO, Benthic Plant Invertebrate and Fish Biodiversity, Great Barrier Reef, Northeast Australia, 2003-2006. 276513 records from MBM - Herbário do Museu Botânico Municipal. 1702 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 63 records from Revision of the ant genus Myrmoteras in the Malay Archipelago (Hymenoptera, Formicidae).. 62015 records from Atlas of Iberian water beetles (ESACIB database). 2 records from Description of Hoplolaimus bachlongviensis sp. n. (Nematoda: Hoplolaimidae) from banana soil in Vietnam. 30129 records from Escarabajos Coprófagos (Coleoptera: Scarabaeinae) de la Colección Entomológica del Instituto Alexander von Humboldt. 3 records from Collection Crustacea - ZSRO. 119 records from Various insect orders, NEF. 1 records from Celaeno spinosa. 233 records from (Table 3) Relative abundances of benthic foraminifera in chosen time-slices from cores obtained in the Nordic and Barents Seas. 201 records from (Table 1) Benthic foraminiferal genera in DSDP Core 95-612-69. 48 records from (Table T2) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1136A. 2983 records from University of Amsterdam (NL) - Páramo vegetation research, Western Andean Cordillera. 3769 records from Eggs Specimen. 960 records from (Table 4) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Site 167-1013 sediments. 47934 records from CRCM Vertebrate Collection. 3 records from Diatom abundance of Hole 38-338, Part 2. 2303 records from (Appendix) Dinoflagellate abundance in ODP Site 202-1233. 150 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2011. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 8579 records from The atlas of breeding birds in Małopolska. 17 records from (Table T4) Calcareous nannofossil abundance of ODP Site 189-1171 sediments. 16 records from (Table V) Distribution of diatoms in samples from Heidemann Valley trench, Antarctica. 13995 records from Herbario Nacional de Plantas Celulares - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 2 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 767 records from Scottish Natural Heritage - Compilation of records of 12 Article 17 terrestrial mammal species in Scotland. 6 records from Arthropoden aus südostalpinen Höhlen. 16195 records from People's Trust for Endangered Species - Hedgehog records 2005-2006: Hogwatch and Rural Landowner surveys. 777 records from INRA-Versailles Arabidopsis natural variants. 78915 records from Biological Records Centre - Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 2412 records from Ohio University Invertebrate Paleontology Collection. 37694 records from Tallinn Botanic Garden. 16 records from (Table 4) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-840C. 13625 records from Colección de Aves de Colombia del Instituto Alexander von Humboldt. 1323 records from Algae (KBRC-AG). 6 records from Total meiobenthos abundance from the Crimea shelf, Black Sea, area I. 91 records from European bison in Białowieża Primary Forest. 2784 records from Harvestmen_of_French_Guiana. 2815 records from Helgeland Museum, Araneae. 527 records from Inventaire floristique de Beza Mahafaly. 4 records from A new carpenter ant, Camponotus parabarbatus (Hymenoptera: Formicidae) from India. 2 records from Hornmilben (Oribatida) [pages 323 to 417]. 4998 records from Ohio State University Tetrapod Division - Amphibian Collection (OSUM). 22978 records from Humber Environmental Data Centre - Humber Environmental Data Centre - Non Sensitive Records from all taxonomic groups. 7 records from (Table 4) Characteristics of the Donax trunculus population on the beach of the Anapa Bay Bar in October 2010. 73 records from (Table 1) Distribution of Upper Cretaceous agglutinated benthic foraminifers in DSDP Hole 20-196. 3 records from New Species of Woolly Lemur Avahi (Primates: Lemuriformes) in Bemaraha (Central Western Madagascar). 1664 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campañas 2009-2010. 270 records from Nematode abundance in cold seep sediments of the Nordic Margins (Nyregga, Styregga, Haakon Mosby Mud Volcano). 1 records from First record of Myotis albescens (Chiroptera, Vespertilionidae) in French Guiana. 2868 records from Tree Diversity and Dynamics of the Forest of Seu Nico (Brazil/MG). 3720 records from Saproxylic Beetles of Ireland. 554 records from Bioblitz 2014 Kalvebod Fælled, Denmark. 2856 records from Alien macro-invertebrates in Flanders, Belgium. 1833 records from (Appendix) Benthic foraminifera distribution of upper Creatceous and Paleocene at DSDP Hole 72-516F. 9792 records from International Collection of Microorganisms from Plants - New Zealand National Microbial Collection. 24 records from Description of the males of Euprosthenops australis Simon, 1898 and Euprosthenopsis pulchella (Pocock, 1902) (Araneae: Pisauridae). 1322 records from PSUZC-Amphibians Collection. 251744 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from Nothrus canaliculatus. 665 records from Nottinghamshire Biological and Geological Records Centre - Nottinghamshire Biodiversity Action Group Brown Hare Survey. 21 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 11371 records from Herbario Museo de La Salle Bogotá (MLS). 78 records from (Table T1) Abundance of dinoflagellate cysts and other palynomorphs in ODP Hole 184-1148A. 1578 records from (Appendix B) Benthic foraminifera in Indian Ocean surface sediments. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 23 records from Revision of the generic classification of the hawkfishes (Cirrhitidae), with descriptions of three new genera.. 1023 records from Greater Manchester Ecology Unit - Invasive and Non-native Species From Greater Manchester. 3276487 records from Insecta of Costa Rica (INBio). 132 records from Fiocruz/CCAMP - Coleção de Campylobacter. 649 records from Countryside Council for Wales - Great Crested Newt (Triturus cristatus) Sites in Wales to 2003. 138472 records from Inventaire National du Patrimoine Naturel : Flore du Limousin. 284 records from Distribution of planktic foraminifera and stable istopes of sediment core MSM05/5_712-2. 11392 records from Danish Plant Bugs (Miridae). 285 records from (Figure 7) Stratigraphic distribution of selected dinoflagellate species in DSDP Hole 93-603B. 3382 records from People's Trust for Endangered Species - Hedgehog Hibernation Survey records. 202 records from Inventario de Aves Buenos Aires, Tauramena, Casanare. 14 records from (Table 2) Abundance of metazoan ice meiofauna in the bottom 30 cm of level sea ice obatined during the 2005 Hidden Ocean expedition. 2172 records from Colección de Reptiles. 24121 records from Endemic plants of the Congo basin. 2 records from Zobellia amurskyensis sp. nov., Zobellia laminariae sp. nov. and Zobellia russellii sp. nov., novel marine bacteria of the family Flavobacteriaceae. 300 records from (Table 3) Distribution of recurrent benthic foraminifera at DSDP Hole 75-530A, from Coniacian-Santonian to Albian. 1 records from On the Chilopoda from Turkey. 2876 records from Naturalis National Natural History Museum (NL) – Mollusca fossils. 411 records from SuLaMa reptile survey I 2012. 1 records from Report on the occurrence of synanthropic derived form of Chrysomya megacephala (Diptera: Calliphoridae) from Royapuram fishing harbour, Chennai, Tamil Nadu, India. 192273 records from Field Museum of Natural History (Zoology) Mammal Collection. 72185 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 1489 records from (Figure 4) Dinoflagellate cyst measured on sediment core AI07-03G. 1 records from Oribates angulatus. 51 records from Packer Collection / Xenochilicola bees, Chile. 439 records from Museu Paraense Emilio Goeldi - Scorpiones Collection. 138 records from (Table 1) Late Pleistocene planktonic foraminifera of Hole 302-M0004C. 8124 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 657 records from (Table 2) Abundance of Miocene to Pleistocene dinoflagellate cysts in ODP Site 133-823. 2217 records from Gothenburg Herbarium - Types (GBIF:IH:GB:Herbarium). 55056 records from Biological Records Centre - Reptiles and Amphibians Dataset. 11762 records from Chrysomelidae of the Carpathians. 584476 records from Joint Nature Conservation Committee - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by JNCC. 994 records from (Appendix B) Dinoflagellate cysts in Southeast Pacific Ocean surface sediments. 15953 records from Algae (S). 1652 records from Depletion Fishing in the river "Grote Nete" and "Kleine Nete" (1989-1996). 18 records from Survey of the native freshwater opossum shrimp (Mysis relicta) in Ireland. 2506 records from Museu Paraense Emilio Goeldi - Opiliones Collection. 3 records from A new killifish genus and species from the coastal plains of northeastern Brazil (Teleostei: Cyprinodontiformes: Rivulidae).. 140 records from (Table 3) Counts of dead (not stained) benthic foraminifera from stations in the northern Gulf of California. 16452 records from Fungus herbarium, UiB. 111682 records from British Phycological Society - Seaweed data for Great Britain and Ireland. 11961 records from Vegetation data from long term sheep grazing experiment in Setesdal, Norway. 146809 records from OHN. 1129 records from Upper Silesian Museum, Insect Collection. 108 records from (Table 7) Planktonic foraminifera species in bottom sediments of Core ML5_348, North Atlantic. 1626 records from Ornithologie ZMK. 79717 records from CSIRO, Soviet Fishery Data, Australia, 1965-1978. 223522 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD Butterfly data up to current day. 1429 records from Schlern - (Bozen). 297 records from Clyde River Foundation - Bullhead (Cottus Gobio) distribution for Scotland, historical to present. 882456 records from SA Fauna (BDBSA). 10255 records from Araneae Collection. 423 records from (Table 2) Benthic foraminiferal distribution at ODP Hole 127-795B. 147466 records from AIMS, Long-Term Fish Visual Census, Great Barrier Reef, Northeast Australia, 1992-2015. 5106 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 30 records from Specimens from India at the University Museum at the University of Bergen. 3 records from Beiträge zur Kenntnis der Oribatiden (Acari) Europas I. Zwei neue Arten der Gattung Suctobelba Paoli aus der Oberlausitz (DDR): Suctobelba scalpellata n. sp. und Suctobelba secta n. sp.. 496 records from (Table 4) Benthic foraminifera in Northwest Indian Ocean surface sediments. 90 records from (Table 2) Occurrence of larger benthic foraminifers in ODP Hole 133-823C. 38 records from (Table T2) Dinoflagellate cysts and pollen/spore yield and preservation in ODP Site 188-1166. 39 records from Arachnologie ZMK. 1 records from Hesperinus ninae Papp & Krivosheina (Diptera: Hesperinidae) from Georgia: the second record of this peculiar species. 3182 records from (Table 15B) Occurrences of planktonic foraminifers in DSDP Hole 90-593, samples 593-31-CC through 593-60-CC. 5856 records from FCAB - Herbário Friburguense. 19 records from Inventaire National du Patrimoine Naturel : Données sur Tamias sibiricus (Ecureuil de Corée). 32109 records from Herbier de Nouvelle-Calédonie. 2 records from Pantopoda SMF. 68 records from Malakologie ZMK. 3 records from A new candidate for a Gondwanaland distribution in the Zodariidae (Araneae): AustralutIca in Africa. 5605 records from Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 12876 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Pectinoidea. 24 records from 10) SST, IRD and benthic foraminiferal d18O data from the Norwegian Sea core MD95-2010: revised chronology for the Last Interglacial (period 134-110 ka). 10 records from A new species and new records of Molophilus Curtis, 1833 (Diptera: Limoniidae) from the Western Palaearctic Region. 220 records from (Figure 1b) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3182. 637399 records from Données ONF Faune-Flore-Fonge. 1 records from Nothrus bispinosus. 5 records from Erethistoides sicula, a new catfish (Teleostei: Erethistidae) from India.. 1 records from Ctenophora ZMK. 1 records from Nothrus bicarinatus. 448 records from (Appendix A) Abundance of ostracode species from DSDP Hole 48-401. 1532 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Skye Estate during October 1995 â October 2004.. 2 records from Bryozoa ZMK. 12 records from Echinodermata ZMK. 3268 records from (Table 1) Distribution of early Eocene to early middle Eocene benthic foraminifera in DSDP Hole 93-605. 1 records from On centipedes (Chilopoda) of Albania, 2. 513 records from Hemiptera (Heteroptera) collection of National Museum of Nature and Science. 396 records from (Appendix) Bathyal benthic foraminifera in ODP Hole 166-1006A sediments. 396314 records from British Lichen Society - BLS Lichen Database: English churchyards. 229 records from Zur Faunistik und Ökologie der Caribiden (Caribidae, Coleoptera) ausgewählter Trockenstandorte in der 'Nuthe-Nieplitz-Niederung' (Land Brandenburg). 1725 records from (Table 1) Planktonic foraminifer stratigraphy in ODP Hole 167-1021C sediments. 281 records from Myriapoda of Costa Rica (INBio). 2 records from Amphibia ZMK. 590563 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 6 records from Vermes ZMK. 1 records from Oribates badius. 195 records from (Table T3) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1210A, Shatsky Rise, Pacific Ocean. 3221 records from Road Kill Survey. 154 records from Specimens from India at the NTNU University Museum in Trondheim. 382 records from Reptilia ZMK. 496203 records from Bees, Wasps and Ants Recording Society - Bees, Wasps and Ants Recording Society - Trial Dataset. 20991 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 1262 records from Crustacea ZMK. 27290 records from Bird Monitoring Data. 104 records from Mammalogie ZMK. 171 records from (Table T1) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1049A. 4 records from Tunicata ZMK. 456 records from (Table 1) Mollusc biostratigraphy of a sediment core obtained near Gross Pampau. 1 records from Description of a new species of Echiodon (Teleostei: Carapidae) from the South Atlantic Ocean.. 10 records from Cnidaria ZMK. 160563 records from CAS Invertebrate Zoology (IZ). 2 records from Porifera ZMK. 111 records from Microplankton abundance measured on water bottle samples during AEGAEO cruise LIA-8. 15925 records from Merseyside BioBank - North Merseyside Other Taxa (verified). 28 records from New provincial records of skinks ( Squamata : Scincidae ) from northwestern Vietnam. 1029 records from Freshwater plants of Cameroon. 1 records from On the Chilopoda from Turkey. 5318695 records from Australia's Virtual Herbarium. 27 records from Hybridization in Umbridae in the Hudson River, New York, with Designation of Neotypes for Umbra limi and Umbra pygmaea.. 3594 records from Visherintroductie - Reintroduction of the fishes chub, dace, burbot, and brown trout in Flanders, Belgium. 83679 records from Scottish Wildlife Trust - Commissioned surveys and staff surveys and reports for SWT reserves. . 335 records from Meiofaunal abundance in sediments obtained during RRS Discovery cruise D297. 2777 records from Plant (KIWE-PL). 9 records from Chenopodium vulvaria. 1 records from Identification of the species of Gnamptogenys Roger in the Americas.. 144 records from Checklist of Fabaceae Lindley in Balaghat Ranges of Maharashtra, India. 270 records from Meiofaunal abundance in sediments obtained during RRS Charles Darwin cruise CD179. 34 records from Caddisfly Records, Edenvale, Co. Wexford 2010. 2625 records from (Table 1) Stratigraphic distribution of planktonic foraminifera from the uppermost Miocene to upper Pliocene in ODP Hole 134-832B. 299492 records from SEAPOP NINA. 5043 records from RSPB - Dartford Warbler national surveys in the UK (SCARABBS). 1667138 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 1 records from Flora of Suriname, volume VI, part I. 1288 records from (Table 4) Distribution of benthic foraminifers from ODP Hole 134-829A. 39 records from Colección de Urocordados. 22 records from A synoptic review of the ants of California (Hymenoptera: Formicidae).. 3061 records from (Table 4) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-846B. 1933 records from Gloucestershire Environmental Data Unit - Gloucestershire BAP Priority Species - Dormouse. 19 records from The first case of aggressive mimicry among lamprologines in a new species of Lepidiolamprologus (Perciformes: Cichlidae) from Lake Tanganyika.. 9 records from A new species of Metahomaloptera (Teleostei: Balitoridae) from China.. 1641 records from NCSM PaleoBotany Collection. 1127 records from Census of the secondary forests of the Lama forest reserve (Southern Benin). 8326 records from Derbyshire Biological Records Centre - Derbyshire Invasive Vascular Plants (INNS) 1900 - 2011. 1 records from Chilopoden und Diplopoden aus Jugoslavischen Höhlen. 50 records from (Table T3) Biogenic and mineral composition of sediments cored in Hamburg-Wulksfelde. 28734 records from UAM Bird Collection (Arctos). 16568 records from Inventaire National du Patrimoine Naturel : Données des campagnes de Suivi Aérien de la Mégafaune Marine (SAMM) de France métropolitaine. 1992 records from (Table 8) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-590A. 2 records from Parioglossus galzini, a new species of ptereleotrid dartfish from Rapa Island (Teleostei: Gobioidei: Ptereleotridae).. 19700 records from RAVON (NL) - Fish observations extracted from historic reports 1860-1907. 377 records from Herbario MAIA, colección de Eucaliptus del INIA-CIFOR. 2 records from Pollen analysis of sediment profile MU01 from Muggesfelder See. 111 records from (Table T5) Relative abundance of Eocene plant microfossil taxa of ODP Site 188-1166. 513 records from Occurrences des observations de la campagne REMMOA Antilles (2008). 61 records from Shrews of Poland. 4 records from New country records of reptiles from Laos. 217 records from Succession of benthic hard-bottom communities abundance at station Errina2012_MDD7. 89 records from Collection Crustacea - PUM. 259 records from (Table 2) Abundances of planktonic and benthic foraminifera in ODP Hole 130-807A. 14420 records from Colección Nacional de Foraminíferos - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1 records from Nothrus convexus. 200 records from Zoological collection of the National Museum. 3762 records from Inventaire National du Patrimoine Naturel : Flore protégée du Dauphiné. 102 records from John Muir Trust - A Lichen Survey of the Ben Nevis Plateau. 2095 records from The Fossil Fish Collection at the Bayerische Staatssammlung für Paläontologie und Geologie. 803 records from (Table 7) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1020B sediments. 308 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 11251 records from Herbarium areqvipense (HUSA). 21091 records from NCSM Birds Collection. 5581 records from IWDG Casual Cetacean Sightings. 163 records from A review of Lamyra Loew (Diptera: Asilidae: Laphriinae). 1329 records from Colección de Invertebrados Cenpat (CNP-INV). 1376 records from Vertical distribution of nannofossils in the section of DSDP Site 72-516. 30926 records from Annelida collection of National Museum of Nature and Science. 2 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2010. 1 records from (List 1) Summary of fossil Mollusca found in Schleswig-Holstein, Germany. 282 records from CSIRO, Cruise SS199402, Marine Biological Survey, Southeast Australia, 1994. 44 records from (Data S1) Palynology of IODP Hole 318-U1360A. 1942 records from Western Australia Museum, Marine Invertebrate Specimens, Ningaloo Reef - Northwest Cape, Northwest Australia, 1952-2004. 453 records from Colección de Fauna Marina del Centro Oceanográfico de Málaga (I.E.O.): CFM_IEOMA. 2223 records from Colección de Zoología Invertebrados - Otros invertebrados. 2224 records from UCM Bird Eggs/Nests Collection (Arctos). 1000 records from Colección Limnológica del Chocó. 749213 records from Historical Bird Atlas. 30 records from Guadeloupe_Taro. 1091 records from (Table 5) Distribution of benthic foraminifers from ODP Site 134-832. 1614 records from Culture Collection of Algae. 9929 records from CHAS Mammalogy Collection (Arctos). 210019 records from Invert Paleo Specimens. 151 records from (Table T1) Biostratigraphy and distribution of Quaternary and Miocene calcareous nannofossils in ODP Site 188-1165. 1415 records from Plant observations from Białowieża National Park. 210 records from (Table 2) Neogloboquadrina plexus coiling direction at DSDP Site 49-410 and Holes 81-552A, 94-610E, and 94-611C. 4601 records from (Table 2) Distribution and relative abundance of mid-Cretaceous planktonic foraminifers at DSDP Site 79-547A. 67 records from Hertfordshire Biological Records Centre - Roadside Verge Survey 1986 (Herts data from Cambs WT survey). 385 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Laridae. 15 records from (Table 15) Calcareous nannofossil occurrences in ODP Hole 130-805C. 688 records from Algae, Norwegian College of Fishery Science. 9 records from Corumbataia britskii (Siluriformes: Loricariidae: Hypoptopomatinae) a new species from the upper Rio Parana basin, Mato Grosso do Sul, Central Brazil.. 2234 records from (Figure 1) Dinoflagellate cyst stratigraphy of DSDP Hole 80-548A. 432 records from Royal Horticultural Society - RHS Hemerocallis gall midge (Contarinia quinquenotata) monitoring. 6 records from Monomorium dentatum sp. n., a new ant species from Egypt (Hymenoptera: Formicidae) related to the fossulatum group.. 1 records from A new myrmicine ant genus from Malaysia with uncertain affinities (Hymenoptera: Formicidae).. 1055244 records from Norwegian Biodiversity Information Centre - Other datasets. 94 records from John Muir Trust - Vascular Plants and Bryophytes of Glen Sligachan. 589 records from Birds (NMNO-BI). 3422 records from The Scottish Ornithologists' Club - Highland Breeding Bird Data 2002-2003 - non-sensitive breeding species. 20404 records from Insect (JNHM-IN). 2856 records from (Table S3) Significant benthic foraminifera species in ODP Hole 164-997A. 829 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2009. 2493 records from (Table T1) Foraminifer abundance of ODP Hole 188-1165B. 58 records from A revision the Australian species of the ant genus Myrmecina (Hymenoptera: Formicidae).. 2 records from On the centipedes (Chilopoda) of the Republic of Macedonia. 8714 records from Greater Manchester Ecology Unit - Bird Records held by Greater Manchester Ecology Unit. 724 records from University of Amsterdam (NL) - Páramo vegetation research, Talamanca Cordillera, Costa Rica. 553 records from Composición florística y estructura de una parcela permanente en bosques humedos tropicales del resguardo Emberá Chontadural, municipio de Mutatá, Antioquia. 9 records from A new species of Margaromantis Piza, 1982 ( Insecta : Mantodea ) from Brazil. 21 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC02. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 2502 records from ISM Herpetology Collection. 8 records from (Table 1) Distribution of benthic foraminifera in GIK_Plankton-B sample. 1602 records from (Table T3) Abundance of dinoflagellates and other palynomorphs in Maastrichtian-Eocene sediments from ODP Hole 189-1172D. 8887 records from Tunicates collection (IT) of the Muséum national d'Histoire naturelle (MNHN - Paris). 337 records from One century of vegetation change on Isla Persa, a nunatak in the Bernina massif in the Swiss Alps. 29513 records from MPM Herpetology. 1 records from Die Chilopodenfauna Griechenlands. 7 records from A new species of the genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae: Dolichoderinae) from Costa Rica.. 23 records from Description of Cathorops manglarensis, a new species from the Colombian Pacific, with redescription of Cathorops multiradiatus (Siluriformes; Ariidae).. 8 records from (Table 1) Maximal abundance of dominating species and phytoplankton groups within the Gelendzhik polygon in 2002-2005. 8 records from Torpedo formosa sp. nov., a new species of electric ray (Chondrichthyes: Torpediniformes: Torpedinidae) from Taiwan.. 7000 records from CCBER Ornithology Collection. 2954 records from Geneva Herbarium – Burnat Herbarium (G-BU). 3 records from Miriapodi cavernicoli del Marocco, della Sardegna e del Piemonte. 7 records from (Table 4) New palynological record of sediments from Odderade. 21694 records from arim. 19 records from (Table S1) Calcareous nannoplankton morphometric analyses performed of Cismon sediment core samples. 6812 records from Invertebrate collection of University of Oulu Zoological Museum. 12 records from (Appendix B) Stratigraphic occurrence of radiolarian special and species groups in sediments of ODP Hole 199-1218A. 3313 records from Dorset Environmental Records Centre - Bryophyte Survey of the Poole Basin Mires - NBN South West Pilot Project Case Studies. 285 records from Sylva Foundation - European Pear Rust (Gymnosporangium sabinae) monitoring. 2061790 records from Museum of Comparative Zoology, Harvard University. 48 records from Tardigrada collection of National Museum of Nature and Science. 718 records from HSU Vertebrate Museum Amphibian Collection. 2 records from A redescription of Lophostica mauriciana Simon, 1902 (Araneae: Salticidae). 12542 records from Herbarium of the Université Libre de Bruxelles. 8102 records from tef-database. 6821 records from Staatliches Naturhistorisches Museum Braunschweig - Coleoptera Collection. 3117 records from Naturalis National Natural History Museum (NL) – Coelenterata. 58044 records from Naturalis Biodiversity Center (NL) - Cnidaria. 1 records from Amycolatopsis marina sp. nov., an actinomycete isolated from an ocean sediment. 1547 records from West Wales Biodiversity Information Centre - Sea Trust Stena Europe Survey of Cetaceans in the St Georgeâs Channel, April 2004- April 2011. 432 records from Plantas Bosque Seco Chicamocha. 91 records from Foraminifera assemblage in surface sediments of the Skagerrak/Kattegat area. 197454 records from Vascular Plant Herbarium, UiB. 12509 records from The Bat Conservation Trust - Hibernation Survey. 56302 records from Kathryn Kalmbach Herbarium. 6211 records from NMMNH Mammal. 197054 records from Ichthyology Collection - Royal Ontario Museum. 320 records from (Figure 1a) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3180. 2087 records from Banco de Germoplasma del Jardín Botánico Atlántico. 120208 records from Inventaire National du Patrimoine Naturel : Poissons d'eau douce de France. 28 records from Colección de Cocodrilos y Caimanes Museo de La Salle Bogotá (MLS). 163 records from Entomofauna laguna El Tinije. 260950 records from USGS PWRC - Native Bee Inventory and Monitoring Lab - US-CA-MX - Bees. 31 records from RSPB - Spotted crake national survey in the UK in 1999 (SCARABBS). 98178 records from CAS Ornithology (ORN). 378 records from Greater Manchester Ecology Unit - Distribution of Badgers in Greater Manchester. 50128 records from Tasmanian Museum and Art Gallery provider for OZCAM. 60 records from The genera of the Neotropical armored catfish subfamily Loricariinae (Siluriformes: Loricariidae): a practical key and synopsis.. 8 records from (Table 1) Major and minor element concentrations in the livers of polar bears (Ursus maritimus) from Canada, Alaska and Greenland. 450 records from John Muir Trust - Species Records for John Muir Trust Properties 2007-2009. 15 records from Chenopodium. 20957 records from CHAS Herpetology. 17 records from Meiofauna abundances in sediments from the Storegga Slide (Norwegian Sea) obtained during the VICKING expedition in 2006. 74 records from SuLaMa reptile monitoring. 164 records from John Muir Trust - Species Records for John Muir Trust Properties Nevis, Sandwood, Quinag and Schiehallion 2010.. 1910784 records from Consortium of California Herbaria. 169 records from The Pteridaceae family diversity in Togo. 6 records from Aristathlus imperatorius Bergroth, a newly recognized synonym of Reduvius iopterus Perty, with the new combination Aristathlus iopterus (Perty, 1834) (Hemiptera: Reduviidae: Harpactorinae) ​. 1245 records from Nematode abundance in sediments obtained during the Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 9787 records from Finnish Entomological Database: Hymenoptera. 154 records from UCM Vertebrate Observations Collection (Arctos). 10046 records from Biological Records Centre - Crayfish (Crustacea; Astacura) data for Britain and Ireland to 2003. 47871 records from H.A. Stephens Herbarium. 4 records from A new ant genus from the southwestern United States.. 314 records from Invertebrate collection of the Seto Marine Biological Laboratory, Kyoto University. 16 records from Mollusca Colelction of the Seto Marine Biological Laboratory, Kyoto University. 752 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 113112 records from Recent Invertebrates Specimens. 2 records from Discothyrea sringerensis (Hymenoptera: Formicidae) a new ant species from India.. 16 records from Moenkhausia pankilopteryx, new species from rio Tocantins drainage, Brazil (Ostariophysi: Characiformes, Characidae).. 13503 records from Collection of various insect orders, Natural History Museum, University of Oslo. 36012 records from VIES - Herbário Central da Universidade Federal do Espírito Santo. 9948 records from Bees of Canada / Gschwendtner property collection. 38841 records from Herbier de Strasbourg. 555 records from (Appendix 1) Abundances of benthic forminifera in ODP Hole 113-689B. 33 records from (Table 6) Distribution and abundance of calcareous-nannoplankton species in the Cretaceous sediments of DSDP Hole 62-466. 60163 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 1150 records from RSPB - Great Yellow Bumblebee sightings data in the UK, 1990 onwards (RSPB, BBCT, HBRG).. 46 records from (Table T2) Stratigraphic distribution of dinoflagellates and pollen/spores by age class, ODP Leg 188 sites. 1808 records from Colección de mamíferos del Museo de Historia Natural de la Pontificia Universidad Javeriana. 55 records from Colección de Platyhelminthes del Museo Nacional de Historia Natural de Chile. 1 records from Nothrus palliatus. 2 records from Ein Beitrag zur Landtierwelt von Korfu. Chilopoda. 4873 records from Berkshire Reptile and Amphibian Group - BRAG - Berkshire Reptile and Amphibian Records. 1109 records from Gloucestershire Centre for Environmental Records - Gloucestershire BAP Priority Species - Water voles. 200913 records from University of British Columbia Herbarium (UBC) - Bryophytes Collection. 1 records from Zetes morticinus. 29171 records from Naturalis Biodiversity Center (NL) - Collembola. 16696 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Fungi and Lichen Observation Records. Pre-2010 for Cumbria.. 1200 records from (Table 5) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1014A sediments. 192907 records from Naturalis Biodiversity Center (NL) - Paleontology Invertebrates. 637 records from Dinoflagellate cysts in western equatorial Atlantic surface sediments. 3319 records from Gloucestershire Centre for Environmental Records - Gloucestershire Amphibians not including great crested newts. 17 records from Hazel Dormouse in Ireland. 1299 records from Waarneming.nl (NL) - Great Grey Shrike Count 2014-2015. 1696 records from Field Study Group of the Dutch Mammal Society (NL) - 2005 - Mammal Survey Pol'ana Biosphere reserve, Slovakia. 157292 records from Hertfordshire Natural History Society Flora Group - Hertfordshire Flora Survey Records 1987-2005. 92 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 6004 records from Colección Limnológica Universidad de Antioquia. 823 records from Líquens d'Andorra. 262 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 211883652 records from EOD - eBird Observation Dataset. 12 records from Dispatch from the field: ecology of ground-web-building spiders with description of a new species (Araneae, Symphytognathidae). 589 records from (Appendix B) Benthic foraminifera extinction group polpulation of ODP Hole 184-1146A. 29691 records from University of Amsterdam (NL) – Benthos monitoring of the North Sea research database. 70111 records from Kyushu University Museum Coleoptera Collection. 876 records from (Supplement 1) Most common taxa or groups of coccoliths from ODP Site 1233 (past dataset) covering the last 70 kyr. 352 records from Universidad de Málaga: MGC-Lichen. 2330 records from Seaweed (Plantae) Collection of the Seto Marine Biological Laboratory, Kyoto University. 319 records from HTSAw - Xiloteca do Trópico Semiárido. 23046 records from Hemipteran specimens of Iwate Prefectural Museum. 30000 records from Birds collection of Yamashina Institute for Ornithology. 47780 records from National Bat Database of Ireland. 42 records from (Fig. 4) Relative proportions of the most abundant chironomid taxa in the Lake Temje sediment core. 493 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 3. 7 records from Pseudochromis lugubris and P. tonozukai, two new dottyback fish species from the Indo-Australian Archipelago (Perciformes: Pseudochromidae: Pseudochrominae).. 4852552 records from Bird Ringing Centre in Sweden (NRM). 22167 records from Natural History Museum Maastricht (NL) - Herbarium. 798 records from Biological Records Centre - Irish Otter Dataset. 1 records from Zetes latipes. 3 records from New species of myrmicine ants from Western Australia (Hymenoptera: Formicidae).. 6 records from Mammalia (JNHM-MM). 1458 records from Waarneming.nl (NL) - Great Grey Shrike Count 2013-2014. 8026 records from Primera caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 1 records from First record of the thread-legged assassin bug Myiophanes greeni Distant, 1903 (Heteroptera: Reduviidae: Emesinae) from India. 976 records from (Table 2) Benthic foraminifera in Pliocene sediments of DSDP Hole 89-586B. 3381 records from (Table 10B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-588A. 175 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1207B. 926354 records from iNaturalist Research-grade Observations. 69622 records from Fundación Miguel Lillo - Colección Entomológica. 807 records from Reunion_Coffea. 18900 records from UCBG TAPIR Provider. 5790 records from CSIRO, Cruise SS200510, Benthic Biodiversity, Western Australia, 2005. 5913 records from An Atlas of Breeding Birds of the Burren and Aran Islands 1993 - 1996. 98 records from Colección Nacional de Heliconias. 13 records from (Table 2b) Species of planktonic foraminifera found in surface layer bottom sediment at Station Vy20-3217GR. 2473 records from (Table 1) Distribution of planktonic foraminifers at DSDP Hole 90-590A. 49637 records from Monitoring data from the federal state Hesse (Germany). 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 3002 records from Colección de Peces Universidad Católica de Oriente. 149 records from (Appendix C) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 160-967A. 2 records from A new species of Cales (Hymenoptera: Aphelinidae) parasitizing Bemisia pongamiae (Takahashi) (Hemiptera: Aleyrodidae) in Taiwan, with a key to world species of the Cales spenceri-group. 25543 records from Colección Nacional de Mastozoología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 5578 records from Caracterización de flora, edafofauna epígea, anfibios y aves del complejo de Páramos de Sotará, Cauca. 2 records from Neue Milbenarten aus Kärnten. 14760 records from Outer Hebrides Biological Recording Project - OHBRP Insects Dataset - Outer Hebrides. 8629 records from National Taiwan University. 73 records from A new handfish, Brachionichthys australis sp. nov. (Lophiiformes: Brachionichthyidae), with a redescription of the critically endangered spotted handfish, B. hirsutus (Lacepede).. 3 records from Mammals (SMNH-MM). 323085 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups.. 1 records from Hypochthonius rufulus. 16572 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 477 records from (Table 2) Distribution of foraminifera in the Miocene section of ODP Hole 133-816A. 2391 records from Ohio State University Tetrapod Division - Reptile Collection (OSUM). 43298 records from Countryside Council for Wales - Pembrokeshire Marine Species Atlas. 3669 records from ARKO strandeng. 1 records from Oribates ovatus. 172126 records from CONN. 27689 records from HUCS - Herbário da Universidade de Caxias do Sul. 17252 records from BioGIS - Vascular plants - HUJ Herbarium. 179 records from (Table 4) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 129-801A. 1077 records from BioGIS - Fish - HUJ collections. 102 records from (Table 1) Planktonic foraminifera counts and stable oxygen isotope ratios of Pacific Ocean surface sediments. 13968 records from NYSM Birds. 14172 records from Biological Resource Center, Department of Biotechnology, National Institute of Technology and Evaluation. 2 records from A remarkable new flightless Madrasostes Paulian, 1975 from Vietnam (Coleoptera Scarabaeoidea Hybosoridae Ceratocanthinae). 1896 records from Cnidaria Collection of the Seto Marine Biological Laboratory, Kyoto University. 1390 records from Caracterización de avifauna de la subcuenca del Río San Pedro, San Pedro, Valle del Cauca. 1369 records from Chromista Collection of the Seto Marine Biological Laboratory, Kyoto University. 1000 records from Mollusca Specimens of Oiso Municipal Museum. 2115 records from Algae specimenｓ database of Shizuoka Prefecture Museum of Natural History. 209 records from (Table 2) Ostracoda community from DSDP Hole 95-613. 2708 records from (Table T1) Benthic foraminfera stratigraphy of ODP Hole 199-1218A and 199-1219A sediments. 85 records from Schulgelände IGS Kaufungen. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 21 records from New species of ant-mimicking jumping spiders of the genus Myrmarachne MacLeay, 1839 (Araneae: Salticidae) from north Queensland, Australia. 3546 records from Dorset Environmental Records Centre - Dorset SW Pilot species dataset. 94 records from (Fig. 3) Inter-core correlation of Ca/Fe ratios and magnetic susceptibility supported by IRD and N. pachyderma (sin) of sediment core GeoB11035-1. 3225 records from Aquatic Oligochaeta of Ireland. 2 records from A new species of Neossos Malloch (Diptera: Heleomyzidae) from the Yukon Territory, Canada, and a revised key to the Nearctic species. 1 records from Hoplophora crinita. 1275 records from (Appendix B) Dinoflagellate cysts eco-groups of DSDP Hole 38-338. 915 records from Colección de Coleoptera (Tenebrionidae) del sureste de la Península Ibérica de la Universidad de Granada. 40481 records from Biological Records Centre - Soldier Beetle and Jewel Beetle (Coleoptera; Cantharoidea and Buprestoidea) records for Britain and Ireland to 2000. 1 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 34 records from National System of Protected Areas in Poland - Fungi. 558827 records from Aranzadi Ringing Scheme (bird ring-recovery data). 9 records from Vigna yadavii (Leguminosae: Papilionoideae), a new species from Western Ghats, India. 89 records from Devon Biodiversity Records Centre - Devon Himalayan balsam data 1997 to 2007. 418 records from Type Collection of the Seto Marine Biological Laboratory, Kyoto University. 8518 records from Upper Silesian Museum, Bird Observations. 22 records from Bacteria Collection of the Seto Marine Biological Laboratory, Kyoto University. 8 records from First record of Neoempheria Osten Sacken (Diptera, Mycetophilidae) biology in the Neotropical region, with associations between its larvae and fungi. 1733 records from Birds collection of Abiko City Museum of Birds. 2043 records from Mollusca Collection of Natural History Museum and Institute, Chiba. 38 records from Inventario de Murciélagos Buena Vista, Jaramá, Yopal, Casanare. 26 records from Nanochromis sabinae, a new cichlid species (Teleostei, Cichlidae) from the Upper Congo River area and Northeast Gabon.. 252 records from (Table T11) Calcareous nannofossil stratigraphy of ODP Hole 198-1212B. 1275 records from (Table T6) Planktonic foraminifera stratigraphy of ODP Hole 198-1209, Zones P12-P18. 164 records from Taxonomy of the catfish genus Pseudoplatystoma Bleeker (Siluriformes: Pimelodidae) with recognition of eight species.. 29 records from A Revision of the Genus Synagelides Strand, 1906 (Araneae, Salticidae) in Korea. 202 records from (Appendix A) Relative abundance of benthic foraminifera in ODP Hole 138-844C. 473 records from (Table 1) Foraminifera abundance of ODP Hole 162-985A sediments. 6774 records from Colección Nacional de Paleopalinología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 242 records from (Supplement 3) Dinoflagellate cyst concentrations of the three transects OMZ (GeoB 12312, 12321, 12331), below-OMZ-seep (GeoB 12326), and OMZ-seep (GeoB 12328). 57928 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Lepidoptera_Nymphalidae_Palearctic. 1594 records from Musée Vert ornithology collection. 21749 records from University of Lethbridge Herbarium (LEA). 5152 records from (Table T1) Plankontic foraminifera stratigraphy of ODP Site 184-1143. 637 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0002B. 13909 records from AM: Terrestrial Insect Collections (1896-2000). 9399 records from Merseyside BioBank - Merseyside BioBank Active Naturalists (unverified). 50000 records from observe_tuna_bycatch_ecoscope. 106 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 71 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2007. 11 records from A new rainbowfish (Teleostei: Melanotaenioidei: Bedotiidae) from the southeastern highlands of Madagascar, with comments on the biogeography of Bedotia.. 43 records from A Unique Nest-Protection Strategy in a New Species of Spider Wasp. 40 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto102-110. 7 records from A new species of Trichomycterus (Siluriformes: Trichomycteridae) from south Brazil and redescription of T. iheringi (Eigenmann).. 4498 records from Flora of Japan Specimen Database. 2754 records from (Table 7) Benthic foraminifera in middle-late Miocene sediments of DSDP Site 90-590. 144765 records from Invertebrates Collection of the Swedish Museum of Natural History. 10339 records from KUBI Ichthyology Tissue Collection. 1900 records from Fungi Collection. 35 records from Hertfordshire Biological Records Centre - Hertfordshire Otter Records 2002 - 2012. 181 records from Alien Species in Poland - Animals. 33173 records from Global Lacustrine Diatoms. 353326 records from UCJEPS TAPIR Provider. 212157 records from Estonian Museum of Natural History. 713 records from (Figure 6) Total organic carbon content and counted dinoflagellate cysts of sediment core GeoB10706-3. 366 records from (Appendix A) Abundance of selected coccolithophores in sediment core DS97-2P, North Atlantic. 11 records from Pollen profile from sediment core AV14_K2-1. 998 records from minsok. 97 records from Birdrace-Die_Bonnapartemöwen-Rhein-Sieg-Kreis. 115 records from RSPB - Bringing Reedbeds to Life Amphibian Survey of two key reedbed sites in England in 2010.. 23 records from First record of the genus Venanus (Hymenoptera: Braconidae: Microgastrinae) in Mesoamerica, with the description of two new species from Costa Rica. 10866 records from Heteroptera of Ireland. 2275 records from UFRN-Fungos - Herbário UFRN - Fungos. 480 records from Spiders_of_French_Guiana. 3065 records from Colección de Ofidios Museo de La Salle Bogotá (MLS). 324 records from People's Trust for Endangered Species - Noble Chafer: Post-BAP records from 1998 onwards. 69 records from Revision of the subgenus Aulacomyrma Emery of the genus Polyrhachis F. Smith, with descriptions of new species.. 66035 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Micro Moths (BNHS) - 1820-2009. 86 records from Appendix A: Results of the pollen analysis of the PG1755 core from Lake Billyakh. 3 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cinclidae. 85 records from Countryside Council for Wales - Welsh Lesser Horseshoe Bat Summer Roost Surveillance Database. 54 records from Three new species of Gastromyzon (Teleostei: Balitoridae) from southern Sarawak.. 1035 records from National Museum Of Marine Science & Technology. 424 records from Field Study Group of the Dutch Mammal Society (NL) - 2011 - Mammal Survey Biokovo Nature Park, Croatia. 4745 records from Collection botanique Le Grand A. (BOUM). 5 records from Notes on the biology, distribution, biosecurity status and history in New Zealand of Macrotrachelia nigronitens (Stål, 1860) (Heteroptera: Anthocoridae). 33 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto57-65. 2966 records from Bolivian Amazon lowland fish metacommunity data. 1 records from A new Camponotus from Madagascar and a small collection of ants from Mauritius.. 923 records from Colección Plantas Vasculares - Herbario del Departamento de Biología, Bioquímica y Farmacia de la Universidad Nacional del Sur. 92 records from Birdrace-Team_BO-bachter-Bochum. 39 records from Kryptopterus geminus, a new species of silurid catfish (Teleostei: Siluridae) from mainland Southeast Asia.. 3 records from Salticidae from the Himalayas. The genus Hasarius Simon, 1871 (Araneae: Salticidae). 4829 records from Coleção de Polychaeta do Museu Nacional. 6884 records from Herbario CDMB - Jardín Botánico Eloy Valenzuela. 4230 records from Derbyshire Wildlife Trust - Derbyshire Wildlife Trust Coleoptera Records up to Dec 2012. 164 records from EcoRecord - Flatworm Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 1 records from Murcia trimaculata. 246 records from CaCO3, biogenic opal, TOC, and microfossil observations of sediment core MR06-04_PC23A. 110017 records from Louisiana State University Herbarium - Vascular Plants. 1752 records from Herbier National de Mauritanie (HNM). 850 records from Shellfish (NHMK-MS). 1087 records from SMNS Palaeontological collection - Tertiary and quaternary invertebrates. 205653 records from Inventaire National du Patrimoine Naturel : Oiseaux nicheurs de France. 949 records from Percentage analysis of dinoflagellate cyst taxa groups from surface sediment samples of the eastern Indian Ocean. 13815 records from DMNS Marine Invertebrate Collection (Arctos). 600 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Accipitridae. 121 records from (Table 2) Relative contents of planktonic foraminifera in bottom sediments from the Ashadze-1 Hydrothermal Field. 1 records from Campylomorphus homalisinus (Elateridae): a new species for Lombardy (Italy), with notes on its ecology, distribution and biogeography. 45 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 85 records from Birdrace-Die_Paradiesvögel-Herford. 2 records from Male sleeping aggregation of multiple Eucerini bee genera (Hymenoptera: Apidae) in Chapada Diamantina, Bahia, Brazil. 11 records from Six new species of the spider family Ochyroceratidae Fage 1912 (Arachnida: Araneae) from Southeast Asia. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 238 records from John Muir Trust - List of Lichen Species recorded on high ground in the Ben Nevis range. 1914 records from Macrophytes_CLF. 1447 records from Odonata of the Congo River 2010 expedition. 80808 records from ALCB - Herbário Alexandre Leal Costa. 690 records from Field Study Group of the Dutch Mammal Society (NL) - 2012 - Mammal Survey Galicia, Spain. 23 records from Trichoribates and Jugatala (Acari: Oribatida: Ceratozetidae) from the Central and Southern Alps, with notes on their distribution. 1489 records from Herbarium Rhoenmuseum Fladungen. 348808 records from Estonian University of Life Sciences. 23215 records from Monitoring data from the federal state Rhineland-Palatinate (Germany). 1 records from Pollen analysis of sediment profile BLA00 from Blankensee. 87 records from Tab. 5: Artenzusammensetzung, mittlere Individuendichte, Diversität und Eveness der benthischen Gemeinschaft. 1 records from A new species of Lathrolestes Förster (Hymenoptera: Ichneumonidae) from Peruvian Amazonia. 9 records from Trichomycterus pauciradiatus, a new catfish species from the upper rio Paraná basin, southeastern Brazil (Siluriformes: Trichomycteridae).. 987 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Thraupidae. 20 records from Botia udomritthiruji, a new species of botiid loach from southern Myanmar (Teleostei: Botiidae).. 25883 records from Monitoring data from the federal state Saxony (Germany). 178 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine): Records of Fossil Molluscs for Great Britain. 15973 records from Vegetation data from sheep grazing experiment at alpine site in Hol, Norway. 98 records from acari. 7 records from An unusual new species of Micraspis Chevrolat (Coleoptera: Coccinellidae) from northeastern India. 1 records from (Table 1) Concentration of PCB and other contaminants in blood plasma of polar bears (Ursus maritimus) from Svalbard. 6 records from Across the Baltic: a new record for an enigmatic black scavenger fly, Zuskamira inexpectata (Pont, 1987) (Sepsidae) in Finland. 693 records from (Figure 2e) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3205. 64 records from (Table 4) Pleistocene nannofossil range chart for ODP Hole 134-827B. 408325 records from University of California Museum of Paleontology. 5 records from A new cleaner goby of the genus Elacatinus (Teleostei: Gobiidae), from Trindade Island, off Brazil.. 617 records from Meiofauna abundance of westerm Mediterranean Sea seep sediments. 86659 records from UCT: Southern African Butterfly Conservation Assessment (1815-2009). 4268 records from Free-living marine Nematodes from Ali, Rada Tilly and El Limite sandy beaches (Chubut, Argentina) 2006.. 8706 records from NINA botanical collection. 24 records from (Tables 1,2) Site characteristics and phenotypic attributes of King Penguins (Aptenodytes patagonicus) on Possession Island. 419514 records from Meadow and Pasture Inventory (SJV). 537 records from The French National Collection of forage and turf species (grasses and legumes).. 1359 records from CSIRO, Cruise SS199701, Marine Biological Survey, South Tasmania, Southeast Australia, 1997. 1 records from Asya hayvanlari ve zoogeografiyasi hakkinda. Asiatische Beiträge. VIII.. 2 records from Acrochordonichthys gyrinus, a new species of akysid catfish (Teleostei: Siluriformes) from Thailand.. 405 records from (Table 5) Range chart of benthic and planktonic foraminifera of ODP Site 127-797. 7 records from Kryptolebias sepia n. sp. (Actinopterygii: Cyprinodontiformes: Rivulidae), a new killifish from the Tapanahony River drainage in southeast Surinam.. 7 records from (Table 5) Concentrations of organochlorine pesticides in adipose tissue of polar bears (Ursus maritimus) between 1991-2007. 68 records from RSPB - Bean geese on the Slamannan Plateau, Central Scotland between 1993 and 1995 (RSPB/SNH/Bean Geese Action Group). 258 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 7046 records from HFSL - Herbário Dr. Ary Tupinambá Penna Pinheiro. 1031 records from Circumpolar Seabird Monitoring Plan. 105 records from (Table 1) Occurrence of Early Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 89 records from Arvenses y árboles asociados a cafetales de Cundinamarca. 19553 records from Wildbook for Whale Sharks. 1244 records from Mosquitoes_of_French_Guiana. 10000 records from Coleccion Entomologica CEI - CCT Mendoza CONICET.. 7 records from Cordylancistrus nephelion (Siluriformes, Loricariidae), a new and endangered species of suckermouth armored catfish from the Tuy River, north-central Venezuela.. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 28 records from (Table 2) Distribution of the endemic fly (Anatalanta aptera) and the introduced ground beetle (Merizodus soledadinus) on the Kerguelen Islands. 25128 records from rmca-albertine-rift-butterflies. 392968 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 4 records from A new genus and species of Acaenitini (Hymenoptera, Ichneumonidae, Acaenitinae) from China. 131642 records from mel. 1 records from Nothrus piceus. 1659 records from MISE Project Waterford Otter Records, 2011-2015. 212 records from (Appendix A) Campanian-Maastrichtian calcareous nannofossils in DSDP Hole 44-390A. 1 records from Zur Kenntnis der Lithobiiden. 43857 records from Mammals housed at MHNG, Geneva. 84521 records from BioGIS - Vascular plants - INPA database. 1 records from Über einige von Jaroslav Storkán in Bulgarien gesammelte Chilopoden. 9526 records from UK Cetacean Strandings Investigation Programme - Stranded cetacean data from Great Britain collected from 01/01/89 through to 31/03/10. 79211 records from KUBI Vertebrate Paleontology Collection. 855 records from (Table 1) Distribution of ostracods in Jurassic sediments of DSDP Hole 79-547. 56 records from Onychophora of Costa Rica (INBio). 5928 records from HUSC - Herbário Unisanta. 34829 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 8785 records from HPBR - Herbário Padre Balduino Rambo. 161 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 138-852B. 544 records from Glasgow Museums BRC - The Changing Flora of Glasgow: Orchid Dataset. 8441 records from Natural England - Batsites inventory for England. 7356 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Moss and Liverwort Observation Records. Pre-2010 for Cumbria. 819 records from Inventaire National du Patrimoine Naturel : CBN de Midi-Pyrénées. 1 records from A new species of Enoplomischus from Kenya (Araneae: Salticidae: Leptorchestinae). 1487 records from (Appendix A) Relative abundance of planktonic foraminifera in ODP Hole 117-723A. 122 records from Birdrace_Gütersloher_Gimpel-Gütersloh. 123 records from Birdrace-Thüringer_Becken-Sömmerda. 168 records from Birdrace-Marburger_Vogelwelt.de-Marburg/Biedenkopf. 2413 records from Literature based species occurrence data of birds of North-East India. 112 records from Birdrace_Die_Borner-Viersen. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 18 records from (Table 3) Foraminiferal species in DSDP Sample 78-541-5-3,19-21. 221428 records from Essig Museum of Entomology. 1266 records from Actinomycetes Collection in BCRC. 613 records from Countryside Council for Wales - Shad Monitoring data. 202811 records from CAS Ichthyology (ICH). 5254 records from Diptera collection (ED) of the Muséum national d'Histoire naturelle (MNHN - Paris). 42517 records from A common plants survey of vascular plants in South Northumberland and Durham, United Kingdom. 13949 records from University of Amsterdam (NL) - Páramo Vegetation Research, Chingaza - Cruz Verde - Monserrate -Guasca, Colombia. 15813 records from The Diatom Collection of Franz Josef Weinzierl at the Botanische Staatssammlung München. 761 records from Dorset Environmental Records Centre - Dorset Heath - NBN South West Pilot Project Case Studies. 39 records from ECOCEAN MantaMatcher. 1166 records from Colección de Saurios Museo de La Salle Bogotá (MLS). 1915 records from Colección de Anfibios Museo de La Salle Bogotá (MLS). 10 records from Redescription of the little-known grasshopper Willemsella (Acrididae, Hemiacridinae) from Peninsular Malaysia. 3327 records from BioGIS - Mammals - SPNI. 205 records from infish. 2432 records from RSPB - Black Grouse Recovery Project Annual Survey in Argyll & Bute 2002-2009 (RSPB/SNH/FCS/Scottish Power). 39766 records from BioGIS - Vascular plants - A. Danin's point database. 1353 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Santa Fé de Antioquia, Antioquia (primer censo). 91 records from (Table T2) Paleocene calcareous nannofossil abundance of ODP Hole 173-1068A. 5549 records from Diplopoda (NSMK-DI). 20 records from Cyatta abscondita: Taxonomy, Evolution, and Natural History of a New Fungus-Farming Ant Genus from Brazil. 129 records from Mammalia (KNAM-MM). 24 records from A new species of Jenynsia (Cyprinodontiformes: Anablepidae) from northwestern Argentina and its phylogenetic relationships.. 6475302 records from NMNH occurrence DwC-A. 18004 records from Census of the animals of Benin. 22224 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 61468 records from Naturalis National Natural History Museum (NL) – Aves_ Passeriformes. 1 records from On the Chilopoda from Turkey. 959 records from SMNS Palaeontological collection - Fossil mammals. 69 records from Occurrence data of Namadytes (Diptera: Asiloidea: Mydidae). 10234 records from Collection entomologique Barthélémy. 169 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of DSDP Hole 93-603C. 208 records from (Table 4) Distribution of recurrent benthic foraminifera at DSDP Hole 75-530A, from Campanian and Maestrichtian. 15927 records from Derbyshire (Derby Museum) Biological Records Centre - Derbyshire & Peak District Protected Species Database (Summary of available records 1970- 2008). 11 records from Himantura hortlei n. sp., a new species of whipray (Myliobatiformes: Dasyatidae) from Irian Jaya, Indonesia.. 8052 records from Estudios bióticos: Plantas, artropofauna edáfica, anfibios y aves del Complejo de Páramos Iguaque Merchán. 10 records from Revision der Ceratozetidae, 4. Ceratozetes mediocris Berlese (Arach., Acari, Oribatei). 1440 records from (Table 21) Benthic foraminifera in middle Miocene sediments of DSDP Hole 90-594. 29264 records from NCSM Vertebrate Paleontology Collection. 27 records from Tejidos de anfibios y reptiles de la ventana piloto Paz de Ariporo - Hato Corozal. 15660 records from DMNS Mammal Collection (Arctos). 252060 records from Moths Ireland. 17447 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 25 records from Countryside Council for Wales - Freshwater Gwyniad Survey Data. 660 records from (Table 1) Benthic foraminifera in late Miocene sediments of DSDP Hole 89-586B. 5450 records from Collection paléontologique du Museum d'histoire naturelle de la ville de Bourges (BOUM). 33 records from (Table 2) Distribution of Cretaceous redeposited benthic foraminifers at DSDP Hole 89-585A. 7 records from (Table T4) Nannofossil counts accross the K/T boundary in ODP Hole 183-1138A. 1 records from Nothrus mutilus. 100 records from PSUZC-Reptile Collection. 1836 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 128 records from Birdrace-Brut-Wetteraukreis. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 19451 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 118 records from Birdrace-Blind_vor_Birds_BVB_Kranenburg07-Kleve. 110 records from Birdrace-LiLaMai-Vechta. 103 records from Birdrace-Borussia_Zippammer-Bad Kreuznach. 101 records from Birdrace-Herford-Birder-Herford. 99 records from Birdrace-Die_EderSeaWatchers_WsndaH!-Waldeck/Frankenberg. 96 records from Birdrace-federleser-Herford. 103 records from Birdrace-Die_Nachtigallen-Herford. 88 records from Birdrace_Die_Polyglotten-Saarlouis. 81 records from Birdrace-Breisgau_Brut-Breisgau/Hochschwarzwald. 33 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from RV Poseidon cruise 334. 257 records from Seewasen. 83 records from Spechtwald. 144 records from Ehmkendorf. 105 records from Feriendorf des Kreises Gedern (Ober-Seemen). 247 records from Quirópteros Asociados al Bosque Seco de la Vereda El Carbonero, Santander de Quilichao, Cauca. 4 records from Pollen analysis of sediment profile WO1 from Wollingster See. 6 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2011. 2052 records from Angelo State Natural History Collections (ASNHC) - Ornithology Collection. 57495 records from TNHC Ichthyology Collection. 209 records from (Appendix A) Palynofacies absoulte abundances of DSDP Hole 38-338. 108 records from Birdrace-TriumVIErat-Viersen. 102 records from Birdrace-Westfälische-Nachtigallen-Recklinghausen. 104 records from Birdrace-RMD_Die_Gipfelstürmer-Main-Taunus-Kreis. 100 records from Birdrace-Meister_der_Herzen-Kleve. 91 records from Birdrace-Die_TUErteltauben-Tübingen. 91 records from Birdrace-Enger_am_Spektiv-Herford. 127 records from Birdrace_Schräge_Vögel-Herford. 102 records from Birdrace-Die_Nachtraben-Stuttgart. 100 records from Feriendorf Ober-Seemen. 100 records from Grenzturm Hohen Neuendorf. 155 records from Hainhoop - Tonkuhle - Bullenmoor (Arpke). 37 records from Berlin - Treptower Park / Karpfenteich. 195 records from Truppenübungsplatz Panzerkaserne Böblingen. 69 records from Schulgarten mit Klasse 8a (Essen). 76 records from Schulgelände des Gymnasiums Nepomucenum (Coesfeld). 150 records from Steinbruch Mainz-Weisenau. 158 records from Panke und Ufer am Kinderbauernhof Pinke-Panke. 22 records from Dellwiger Bach (Dortmund). 46 records from Hainbachtal in Oelsnitz/V.. 106 records from Schulgarten Hans-Carossa-Oberschule. 59 records from Rund ums Ökohaus (Würzburg). 99 records from Düne am Ulvenberg (Darmstadt). 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 34 records from Hangwiese bei Tussenhausen Klassen 1 a und 1 b. 1037 records from Countryside Council for Wales - Rare Flowering Plant and Fern Data. 5 records from Streuobstwiese (Mittelgasse 4). 2916 records from Orthoptera (Grasshoppers & Crickets) & allied insects of Ireland. 3 records from Achaeta becki sp. nov. (Oligochaeta: Enchytraeidae) from Amazonian forest soils. 376 records from (Table 1) Distribution of planktonic foraminifera in the Cretaceous succession of DSDP Hole 95-612. 523 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Ardeidae. 96 records from (Table 2) Neogene benthic foraminiferal community at DSDP Hole 95-613. 19309 records from Mammal collection, Natural History Museum, University of Oslo. 128787 records from Seed and Leaf Beetle Recording Scheme - Bruchid and Chrysomelid Distributions in Britain and Ireland: pre 1900, 1900-1979, 1980 onwards. 638 records from EcoRecord - Fish records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 120 records from Birdrace-Kosmos_Racer-Freising. 150 records from Birdrace-Ostseevögel-Ostvorpommern. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 120 records from Birdrace_Steckbyer-Auenländler-Anhalt_Zerbst. 114 records from Birdrace-Finkenspötter-München. 111 records from Birdrace-Uhulogen-Lippe. 109 records from Birdrace-Team_Charadrius-Günzburg. 104 records from Birdrace-Diesmal_sehen_wir_mehr-Lippe. 95 records from Birdrace-Buteo1_DO-Dortmund. 94 records from Birdrace-Resopal_Altkreis_Dieburg-Team-Darmstadt/Dieburg. 88 records from Birdrace-WeserEggeLäufer-Höxter. 90 records from Birdrace-Uttenreuther_Spatzenzähler-Erlangen/Höchstadt. 84 records from Birdrace-Haubenpirole_vom_Biomarkt_West-Tübingen. 67 records from Birdrace-Guckers_Offenbach-Offenbach. 137 records from VFD-H: Rheingau: Pferdeweide Loock. 185 records from Klasse 3a. 241 records from BIRDRACE RennVögel Münsterland. 162 records from Siegen/ Gymnasium Am Löhrtor. 2 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 198 records from FNL e.V.. 342 records from Kremmer Luch. 271 records from Beweidungsprojekt an der Nesse. 50805 records from Plant Specimen from Herbarium (NAS) in China, Institute of Botany, Jiangsu Province and Chinese Academy of Sciences. 122 records from Kloster Eberbach. 70 records from Lech 2001. 2813 records from Araneae collection (AR) of the Muséum national d'Histoire naturelle (MNHN - Paris). 34 records from Borkhart. 360 records from Küstenschutzwald. 114 records from Flora. 80 records from Förderzentrum Schmölln. 97 records from LauWi. 151 records from Isarufer. 52 records from Fledermaus. 55 records from Waldsee. 87 records from Biotop "Kohlbeke" (Berlin-Marzahn). 57 records from Heidesee / Halle. 55 records from Von A(horn) bis Z(ecke) des WWP Chemnitz. 103 records from Fuchsloch (Mohlsdorf/Ostthüringen). 101 records from Naturgrundstück (Eutin). 28 records from Hecke - Klassen 2 a und 2 b VS Tussenhausen. 233 records from Föhrenried (Fronreute und Baindt). 52 records from Caracterización vegetal de una zona de alta montaña (litoral de San Juan) como herramienta de proyección para el establecimiento de una figura de conservación en el chocó biogeográfico. 270 records from Regenrückhaltebecken (Zeulenroda). 23 records from Alter Nördlicher Friedhof (München). 313 records from Stadtpark Herzberg (Elster). 108 records from Gelände der Lahntalschule Biedenkopf und Lahnauen. 56 records from Zitadelle Berlin-Spandau (7b). 64 records from Kabelskebach (Kabelsketal, Saalkreis). 36138 records from Colección Nacional de Invertebrados - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 308 records from Wangerooge. 10 records from Kita-Wäldchen Fuchsturmweg Jena. 101 records from Naturhausgarten. 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 64760 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 149 records from Wirbach. 253 records from Geschützter Landschaftsbestandteil - GLB "Troppach". 180 records from Paul-Gerhardt-Schule Dassel. 183 records from Westerwälder Umwelt- und Naturschutztag Limesgemeinde Hillscheid. 107 records from Landschaftsschutzgebiet Buchhorst 3. 122 records from Stever. 18 records from Spielwiese. 12 records from Kindergarten. 117 records from Wassermann. 79 records from GymnQuerfurt. 43 records from Gewässeruntersuchung Grötzinger Baggersee. 54 records from Zentralfriedhof (Wien). 271 records from Dierloch, nördlicher Mooswald (Freiburg-Hochdorf). 113 records from Hochschulgelände (Bremen). 44 records from "Schlechteberg" Ebersbach/Sa.. 69 records from Kinder- und Jugendferiendorf des Kreises Groß-Gerau - Gedern/Ober-Seemen. 69 records from Lassentiner Moor (Niepars). 245 records from Kiesgruben Wemb. 84 records from Roter Berg Werdau (Leubnitz). 57 records from Waldhusener Moor (Lübeck-Kücknitz). 282 records from Deponie Klausdorf. 20 records from Motzener Tonsee. 6 records from Der Wiesenpark in Oschersleben - ein Arboretum mit eigener Ästhetik. 130 records from Schulgelände Gebrüder-Grimm-Schuleund Umgebung (Lingen). 167 records from Zielbach (Töll). 65 records from Gemeinschaftsgarten Deluxe (Bernburg). 45 records from Flusswerder in der Weser (Hameln). 66 records from Wedeler Au. 170 records from Bodenseeufer Radolfzell. 325 records from Triebesbach (Zeulenroda-Triebes). 95 records from Ortelsbruch - Hangmoor bei Morbach. 57 records from verschiedene Kleingewässer um Oldenburg/Holstein. 69 records from "Schwarzes Teich" (Waldpark Radebeul). 375 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 9 records from "Ach, du dicke Eiche", Wald an der Oste-Grundschule Heeslingen. 41 records from Örtzemündung (Stedden). 96 records from Die Wuhle. 112 records from CommunicA Koblenz - Wildkräuterexkursion - Rheinsteig Bornhofer Höhe. 264 records from Natur erleben rund um den Seminarbauernhof Gut Hohenberg. 113 records from Rund um das LUGY. 31 records from Nationalpark Harz Schul-AG Braunlage. 50 records from Junge Heide, Radebeul/Dresden. 85 records from Insektenvielfalt Ahe/Weichelsee. 54 records from Ludwigshofen. 9 records from Willersalpe. 79 records from Balkon (Norderstedt). 1 records from Papilio Sticheli nov. spec. aut subsp.. 111 records from Ökologischer Weinberg (Guntersblum). 26 records from Quellgebiet Flossach - Klassen 4 a und 4 b VS Tussenhausen. 160 records from Wirbach-Taubental (Bad Blankenburg). 107 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 40 records from Streuobstwiesengelände St.Meinrad Gymnasium. 17 records from Schutzgebiet Ochtersum. 22 records from Heilpflanzen im Hainbachtal. 5036 records from Herbarium specimens of Association des Naturalistes de la vallée du Loing (ANVL). 97 records from Döchtbühlwald (Bad Waldsee). 15 records from AKG-Bensheim. 263 records from Artenvielfalt Kreis Gießen. 74 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 86 records from Besonderer Ort - besondere Natur: Die Mainzer Zitadelle. 248 records from Verwilderter Hausgarten mit angrenzendem Gelände (Laufenburg-Hochsal). 39 records from Südpark (Bochum-Wattenscheid). 54 records from Wiese am Unterbecken. 161 records from Schulgelände Paul-Gerhardt-Schule-Dassel. 219 records from Umgebung der Grundschule Oderberg. 145 records from privater Garten. 86 records from Alter Kreidebruch Saßnitz/Rügen. 161 records from Schussenaue bei Berg. 304 records from Ried und Sand - Artenvielfalt durch Beweidung. 71 records from Bolzplatz. 63 records from Erft in Selikum (Neuss). 73 records from Varnhalt. 18 records from Mittelstreifen. 108 records from Mainufer. 163 records from Brander Wald (Stolberg). 18 records from Dachterasse Realschule St. Bernhard (Bad Mergentheim). 35 records from Urwald 3 (Bad Waldsee). 41 records from Wiese und Bach beim Unterbecken (Markersbach). 303 records from Garten J. Scherrer (Lachen-Speyerdorf). 62 records from Tag der Artenvielfalt BUND Kaiserslautern. 28 records from ISTOTA - Schulgarten in Krakau, Stadtteil Ludwinow. 30 records from NABU VG Weilerbach - NSG Mehlinger Heide, FFH-Gebiet. 163 records from Schulhof der Astrid-Lindgren-Schule Elmshorn. 297 records from Naturparadies in Gräfenhausen am Trifels (bei Annweiler). 51 records from Revision of the Nearctic endemic Formica pallidefulva group.. 61 records from Artenvielfalt auf der Wiese. 55 records from Flora und Fauna am Mittelrheintal. 60 records from Schafsweide Seniorenhaus Berghof. 214 records from Binsenwiesen. 136 records from Grillhütte Wettsaasen, Wiese, Hecken. 94 records from Kochertgraben II. 172 records from Dalbekschlucht. 80 records from VFD-RP: Taunus: Ponykoppel Thurner. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 153 records from Landschaftsschutzgebiet "Holmer Sandberge". 32 records from Schulhof Sandhofenschule (Mannheim). 124 records from Wiesenbiotop am Wasserturm. 181 records from Spießwoogtal / Königsbruch (Fischbach). 212 records from Artenvielfalt im Beckerbruch (Dessau). 103 records from Wasserwerkspark (Chemnitz). 28 records from Sandgrube Zaisertshofen. 13 records from Botia kubotai, a new species of loach (Teleostei: Cobitidae) from the Ataran River basin (Myanmar), with comments on botiine nomenclature and diagnosis of a new genus.. 103 records from Schwanseepark (87645 Schwangau). 48 records from Trockenrasen bei Dörndorf. 77 records from Trockenrasen Franzigmark (Halle/Saale). 49 records from Schulgartengelände des Hans-Carossa-Gymnasiums (Berlin). 68 records from Schulhof der Astrid-Lindgren-Schule (Elmshorn). 4 records from Arthropoden aus südostalpinen Höhlen.. 65 records from Mauernacker (Wettsaasen). 104 records from Außengelände KITA "Mäuseburg" Waldkirchen. 11 records from Desarrollar las actividades tendientes al manejo, conocimiento y conservación del Comino crespo (Aniba perutilis hemsl.), formuladas en el plan de conservación para la especie en el departamento del Meta. 171 records from Biodiv-Camp Sandmagerrasen in Nürnberg/Langwasser. 99 records from Dorfrand Mauderode. 110 records from Obstwiese Osterberg. 4 records from Schulbiotop und Brigach (Villingen). 81 records from Umgebung des Spalatin Gymnasium Altenburg. 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 19 records from Goethe-Hauptschule/Projekt I-10. 28 records from Uferzone Wipper (Biesenrode). 139 records from NSG Leist bei Ziegenhain. 40 records from Flächennaturdenkmal Grubditz. 62 records from Amtsrain Apolda-Zottelstedt. 82 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 28 records from Hainbachtal bei Oelsnitz / V.. 244 records from WildesMoor bei Schwabstedt. 53 records from Weidegut Rechab. 82 records from Mainfränkischer Trockenrasen und Naturschutzgebiet Höhfeldplatte bei Veitshöchheim. 147 records from NABU-Auerochsenweide. 58 records from Weidewirtschaft. 881 records from Moluscos Marinhos de Augusto Nobre. 25 records from Aachen: Exkursion essbare Wildkräuter/UTROPIA. 194 records from Landschaftsschutzgebiet Eulenkopf (VG Otterbach). 59 records from Oschenberg, NO von Bayreuth-Laineck. 97 records from Natur-Erlebnis-Kindergarten Waldkirchen/Erzgebirge. 153 records from Selztal bei Friesenheim. 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 22 records from Breitkopfbecken (Berlin-Reinickendorf). 245 records from Gieselbachtal Fulda-Harmerz. 43 records from Saalewiesen Naumburg. 48 records from Weide am Ostufer des Zotzensees, Müritz-Nationalpark. 101 records from Isartal Dingolfing. 92 records from Birkenloh. 93 records from Höltigbaum. 160 records from Waldstück Bremerhagen LK Bio Kl. 12. 98 records from Rund ums Cani. 61 records from GE-Brühl. 107 records from vegoek. 207 records from Biosphäre Bliesgau. 46 records from (Table 4) Biomass of (benthic) amphipods in the Bering and Chukchi seas. 69 records from Entdeckertour am Muldestausee 1/05. 54 records from Weidegebiete in der Selzrenaturierung. 141 records from Birdrace-Asiola_Quartett-Nordwestmecklenburg. 134 records from Birdrace-Team_Havelland-Havelland. 127 records from Birdrace-Alb_Donaumoos_Kompetänzteam-Alb-Donau-Kreis. 128 records from Birdrace_turbine_untersee-Konstanz. 110 records from Birdrace-Göttinger_Sozialbrachvögel-Göttingen. 94 records from Birdrace-Erlanger_Piepmätzchen-Erlangen/Höchstadt. 133 records from Wulfsmuehle/Pinnau. 2 records from New distribution records for the rare genus Afrotremex Pasteels (Siricidae: Hymenoptera) and provision of interactive Lucid identification keys to species. 39 records from Soolbach-Tal. 97 records from Landschaftspark St.Leonhard-Deisendorf. 122 records from Birdrace-Hügelland-Mainz/Bingen. 100 records from Birdrace-ImmerWiederhopf-Lörrach. 299 records from (Tables 1-15) Morphometric characteristics of the genus Hinia (Nassariidae, Gastropoda) in the Tertiary of northwest Germany. 77 records from Birdrace-Naturschutzscheune-Darmstadt/Dieburg. 85 records from Birdrace-Halsbandschnäpper-Stuttgart. 23 records from Wiese Niederaula. 16505 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine): Compilation of records of rare and scarce species for Great Britain and Northern Ireland. 50 records from Artensuche auf den Elbwiesen in Radebeul. 98 records from Warnowtal (Rostock). 43 records from Schulgelände Thurmair-Gymnasium. 233 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 95 records from Vielfalt verschiedener Wiesen. 155 records from Bammentaler Duft- und Heilkräutergarten. 98 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 166 records from Steinbruch Mainz-Weisenau, 3. Jahr. 40 records from Öhmdwiesen und Göldern (Konstanz). 87 records from Hartholzaue an der Dreisam (Freiburg/March-Hugstetten). 5 records from Naturschutzgebiet Ahrmündung (Remagen). 96 records from Birdrace-Berlin_Sparrows-Uckermark. 42 records from sbosch. 36 records from Selz (Ingelheim am Rhein). 58 records from Schulgelände Kranich-Gymnasium (Salzgitter). 26 records from Kinderbauernhof Pinke Panke - Berlin Pankow. 21 records from Bach. 71 records from Birdrace-do_elster_Dortmund. 81 records from Stadtpark Schmölln. 58 records from Schulhof der Astrid-Lindgren-Schule und Umgebung (Elmshorn). 51 records from Schrebergarten Düsseldorf Oberkassel. 31 records from Regenwasserabfangbecken. 10 records from Ökowerk Emden. 23 records from Schulgarten der Hainbuchenschule (Hagenbach). 24 records from Schulgelände der Waldorfschule Vordertaunus in Oberursel. 24 records from Kaisertal. 48 records from Heider Bergsee (Brühl). 22 records from Kaltenkirchen Brache. 20 records from Mikroorganismen. 23 records from Tümpel Schulbiologiezentrum. 29 records from Insekten. 719 records from IBF Monitoring of Plant Galls. 7 records from Stadtrandlandschaft Apolda-Nord. 6717 records from LSUMZ Mammal Tissues. 2 records from Stadtrand Berlin - Altglienicke/ Was krabbelt auf unserem Abenteuerspielplatz?. 3 records from Blankenfelder See. 16006 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Peces Continentales. 80 records from Landschaftsschutzgebiet Schmutterwald. 2814 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 2 records from Oribatids from Switzerland VII (Acari: Oribatida: Mycobatidae 1) (Acarologica Genavensia XCIX). 70 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 63 records from Hochschule Zittau/Görlitz. 47 records from Neanderthal. 86 records from Naturerlebnisraum Koppelsberg (Plön). 15 records from Regenwasserabfangsbecken (Erlenbach). 257 records from Dinocyst occurrences and zonations from IODP Hole 313-M0028A. 193 records from Gelände des Schulzentrums am Himmelsbarg. 87 records from VFD-H: Heidenrod: Pferdeweide Mürth. 60 records from NABUGEO1. 355 records from Carábidos (Coleoptera: Carabidae) del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 10 records from Feuchtwiesen Wippertal bei Wippra. 20 records from Hübsche Kröten, Wetterfrösche und andere Froschnaturen. 155 records from Birdrace-Usedommeln-Ostvorpommern. 9871 records from Dumfries and Galloway Environmental Resources Centre - Micro-moths distribution for Dumfries and Galloway. 110 records from Birdrace-Alle_Vögel_sind_schon_DADA-Uckermark. 12 records from Naturschutzgebiet Swistbachaue (Eckendorf). 54 records from Bäche, Quellen und Teiche im FFH-Gebiet Mühlhauser Halde. 118 records from Birdrace_FliegendeFüchseLBSGescher-Münster. 120 records from Birdrace-The_early-Birds-Minden/Lübbecke. 100 records from Birdrace-The_Ringers-Friesland. 281 records from Hertfordshire Biological Records Centre - Hertfordshire Wildlife Site Monitoring Surveys (incomplete). 83 records from Birdrace-Team_Eckhard_Reinstein-Hersfeld/Rotenburg. 79 records from Birdrace-Bielefinken-Bielefeld. 53 records from Bad Bodenteicher Heide. 102 records from Industriebrache (Kempen). 74 records from Steinberg in Heidelberg-Handschuhsheim/Falgen. 142 records from Kinderbauernhof Pinke-Panke. 1346 records from EcoRecord - Fungi & Lichen records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 28 records from Schulgelände Freiherr-vom-Stein-Gymnasium (Hamm). 70 records from Birdrace-WdW-Wilder_Westen-Viersen. 78 records from Birdrace-Die_Laufenten-Braunschweig. 66 records from Schulhof A.-Lindgren-Schule (Elmshorn). 47 records from Revised diagnosis of the genus Bangana Hamilton, 1822 (Pisces: Cyprinidae), with taxonomic and nomenclatural notes on the Chinese species.. 16 records from A review of the systematics of western North Pacific angel sharks, genus Squatina, with redescriptions of Squatina formosa, S. japonica, and S. nebulosa (Chondrichthyes: Squatiniformes, Squatinidae).. 1894 records from Colección viva Jardín Botánico Universidad Tecnológica De Pereira. 172 records from Leben im Finkensteiner Moor. 169 records from Birdrace-Cuxland_Schwenke_GeoConsult-Cuxhaven. 217 records from Birdrace-Ornis_im_Einsatz-Lahn-Dill-Kreis. 113 records from Staatsforst Rehna - Woitendorfer Wald im Biosphärenreservat Schaalsee. 13 records from Garten Hamburg Uhlenhorst. 31 records from Blumenwiese und Heckensaum , Kornberg (Gruibingen). 57 records from Schulgarten Fichteschule. 46 records from 8c. 47706 records from University of British Columbia Herbarium (UBC) - Lichen Collection. 221 records from Römertal (Steinpleis). 21 records from Riedkanal Bötzingen. 67 records from Weide an der Mosselde / Dortmund-Kirchlinde/Westerfilde. 36 records from Plöwener Wald. 36 records from Mittelriede Höhe Gliesmarode-Braunschweig. 64 records from Pilzlehrwald. 117 records from Naturschutzgebiet Kochertgraben. 26 records from Erhard Sopp. 21 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 14 records from Three new species of the seasonal killifish genus Simpsonichthys, subgenus Hypsolebias (Teleostei: Cyprinodontiformes: Rivulidae) from the rio Paracatu drainage, rio São Francisco basin, Brazil.. 24 records from Ornithologische Wanderung um Tussenhausen. 80 records from Lahnufer in Villmar. 8 records from Kleiner Ziergarten Winzingen (Neustadt). 7 records from Schulhof A.-Schweitzer Schule (Wetzlar). 12 records from Kinderwald Hannover. 18 records from Wahner Heide - GK 12 Bio Gymnasium Köln-Deutz Thusneldastraße. 13 records from Warnowufer Groß Klein. 16 records from Im und um das Schulhaus. 5 records from Feuchtwiese. 15 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 15 records from Urwald 2 (Bad Waldsee). 15 records from Tiere. 8 records from Eichendorf Weiher Schwalbach a.Ts.. 1 records from Waldtag in und um Seelingstädt. 174 records from Colecciones Zoológicas de la Universidad de León, Colección de Gasterópodos. 249 records from Schule Sulzbach (Oberegg). 53 records from Birdrace-Die_Tigerenten-Erlangen/Höchstadt. 89 records from Birdrace-Team_Wangerooge-Friesland. 102 records from Birdrace-OAG_Neuwerk-Hamburg. 62 records from Zoo Frankfurt. 31 records from Kurler Busch (Scharnhorst). 12 records from Anatomical investigation of the slender catshark Schroederichthys tenuis Springer, 1966, with notes on intrageneric relationships (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 39 records from Stausee Weiditz. 65 records from LSG "Großes Bruch". 48 records from Morphologische Daten von Natrix. 16 records from Streuobstwiese Am Kalkofen, Hirschhorn (Kreis Kaiserslautern). 63 records from Sternwiese Mülheim-Broich. 81 records from Artenvielfalt im Schlosspark Sayn (Sayn/Bendorf). 81 records from Birdrace-Die_Ornithomaten-Herford. 829 records from Cambridgeshire & Peterborough Environmental Records Centre - Chippenham Fen Moth surveillance project. 29 records from Naturerfahrung. 51 records from Steinbachtal (Würzburg). 24 records from Schulhof der Hermann-Runge-Gesamtschule (Moers). 87 records from Klütwald. 40 records from Schulhof Liebfrauenschule Oldenburg. 57 records from Garten in Schmölln. 53 records from Alter Lagerplatz und Gartenteich (Dortmund/Hörde). 49 records from Dörnberg. 36 records from Feuchtbiotop, Wildtier- und Artenschutzstation Sachsenhagen, Sielmanns Natur-Ranger. 39 records from Regenrückhaltebecken Bad Bevensen. 84 records from Streuobstwiese Haus Zeitz. 27 records from Vögel. 101 records from Hoher Stein Kallenhardt. 51 records from Mühlenbach bei Buxtehude. 36 records from Ruhrwiesen Arnsberg, Klasse 9 und 10, Fachbereich Biologie. 66 records from Selz-Renaturierung (Hahnheim/Sörgenloch). 36 records from Schulgelände Lise Meitner Realschule (Paderborn). 29 records from Brenz (Heidenheim). 23 records from Ackerrain Plönhagen. 19 records from Glemstal (Leonberg). 20 records from Lerchenauer Baggersee (München). 10 records from schlittschuhweiher. 11 records from Baumbach Arnsberg, Klasse 12, Fachbereich Biologie. 4 records from Weser und Weseraue bei Höxter, Godelheim und Boffzen. 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 36 records from Salzwiese Diekskiel. 22 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 47 records from Schulgelände Ceciliengymnasium. 4483 records from MVZ Bird Observations (Arctos). 64 records from Schafheide im Böblinger Wald. 15 records from Die geheimnisvolle Welt der Spinnen. 21 records from Tauchen und Meer 02. 45 records from Schulgelände Hans-Carossa-Gymnasium (Berlin). 35 records from Gym Freyung. 13 records from Tiere im Teichgebiet. 22 records from Bachabschnitt der Nette (Osnabrück). 15 records from Naturschutzgebiet Ahrschleife (Altenahr). 141 records from Draubiotop Lavamünd. 70 records from Birds (SMNH-BI). 102 records from Spreewaldfließe und Feuchtwiese bei Lübbenau. 11 records from Waldgebiet Todtnau- Sonnhalde. 81 records from Schulgarten-St.-Georg-Gymnasium. 57 records from Mauervegetation,Flechten und anderes. 56 records from Estetal (Buxtehude). 64 records from Issumer Fleuth. 26 records from Schulteich Heinrich-Mann-Schule. 27 records from Zwickau- Schwanenteich. 32 records from Nationalpark Harz Juniorranger. 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 1174 records from Sudeniederung (Amt Neuhaus). 68 records from Streuobstwiese. 23 records from AKG-Gelände in Bensheim. 5 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 36 records from Olympiapark (München). 28 records from Stadtpark Prinzengarten (Sigmaringen). 1 records from Hoplophora ardua. 15 records from Beisetal bei Niederbeisheim. 27 records from Wiese hinter der Schule (Darmstadt). 709 records from Upper Silesian Museum, Bird Collection. 15 records from Bodentiere rund um die Schule. 64 records from Wiese - Schulgelände des Franziskusgymnasiums (Lingen). 13 records from Eintauchen in die Natur /Harraser Weg (AWO - Kita Oberheldrungen). 15 records from Auf Feld und Wiese / Bretlebener Weg (AWO - Kita Heldrungen). 3 records from Naturschutzgebiet Quellgebiet Swistbach (Gelsdorf). 6 records from Fließgewässeruntersuchung am Haselbach. 45 records from Georgs-Padd (Wangerooge). 8 records from Mit allen Sinnen durch den Wald / Schmücke (ev. Kita Heldrungen). 5 records from Naherholungsgebiet Lange Erlen (Riehen/Basel). 8 records from Krittenhorster Wald (Ostkilver). 13 records from Kleinsäuger der Mergelgruben Misburg (Hannover). 11 records from Kirschfest (Grundschule Heldrungen) / Kirschberg Oberheldrungen. 9 records from Wiesendreieck Luckenwalde. 1 records from Graureiher in Lans. 34 records from Wattenmeer-Safari (Wurster Watt). 344 records from Meiofaunal abundance in sediments obtained during Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 42 records from Kleinstbiotop mit Schulteich/Weißwasser. 6 records from Sächsische Schweiz (Pfaffenstein). 442 records from Nematode abundance in sediments obtained during RRS Discovery cruise D297. 27 records from Bäche im Mooswald (Vörstetten). 17 records from Kohlbach (Sulzfeld). 24 records from Tauchen und Meer. 18 records from Naturtag. 10 records from Bachpatenschaft Beeke. 12 records from Ohemoor (Hamburg/Norderstedt). 12 records from Trockenmauern am ehemaligen Weinberg (Gelnhausen). 94 records from Landschaftsschutzgebiet Buchhorst 4. 5 records from Streuobstwiesengebiet (Kreis Ahrweiler). 2 records from LSG Saale, Rößewiesen (Bernburg/Saale). 1 records from Wiese, Wiesengebiet, Schiffdorfer Damm. 61 records from Rotes Steigle (Panzerübungplatz Böblingen). 5 records from Schulinnenhöfe (Gelsenkirchen). 135 records from Waldi-Weiher. 5 records from Schulhof Montessori Schule (Rotenburg / Wümme). 1 records from Haslauer Moor. 2 records from Hildener Heide - Spörkelnbruch (Haan). 6 records from Boimstorfer Sundern. 1 records from Fledermäuse über der Alster (Hamburg). 24469 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Anfibios. 511 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 140 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 52 records from Naturschutzstation Weinberghaus (Dessau). 359 records from Pöhlberg bei Annaberg. 274 records from Bernhardsthal. 90 records from VFD-RP: Taunus: Kirchenweide Köpplers. 40 records from Glacial cold-water coral: ages, isotope concentrations and ratios. 23 records from Wattuntersuchung (Cuxhaven). 17 records from Tierpark Zittau. 22 records from Altendorfer Dorfbachhöhle / Sächsische Schweiz. 41 records from Nachtaktiv im Ökogarten (Bad Waldsee). 14 records from Lauchhamer GEO-Tag der Artenvielfalt. 11 records from Privatteich(St.Leon). 2 records from Grenzdenkmal Hötensleben - wo früher Grenze wa(h)r - bewahrte Vielfalt. 40 records from Tiere und Pflanzen um uns herum !. 44 records from NW-Innenhof Gesamtschule Herten 7.6.2001. 15 records from Kirchheller Heide ( Bottrop). 4 records from Sächsische Schweiz (Wehlener Gebiet). 59 records from Schulteich Freie Waldorfschule Darmstadt. 16 records from Naturschutzgebiet "Gellener Torfmöörte" (Landkreis Wesermarsch). 9 records from Innenhöfe der Gesamtschule Berger Feld/ Gelsenkirchen. 11 records from Vögel im Garten Kindergarten Zaisertshofen. 12 records from Schulgelände Erich-Kästner-Schule. 4 records from Neues Testprojekt. 163 records from Tiere und Pflanzen am Pfannenbach. 1 records from Karpfenteich, Klasse 6d. 1 records from 5. Wiener Gemeindebezirk. 5 records from Fledermäuse u. nachtaktive Insekten. 295 records from (Table 3) Range chart of benthic and planktonic foraminifera of ODP Site 127-795. 255 records from Colecciones Zoológicas de la Universidad de León, Colección de Bivalvos. 1462 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Flora Vascular Amenazada. 1120 records from Dpto. de Zoologia y Antropologia Fisica, Universidad de Murcia. 555 records from FFH-Gebiet "Calwer Heckengäu". 89 records from Schulgelände Paul-Gerhardt-Schule. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 13 records from Tag der Artenvielfalt am Bruckenwasen. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 107 records from Müritz-Nationalpark. 718 records from Zukünftiges NSG Höftland/Bockholmwik. 410973 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Aves Reproductoras. 91331 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Mamíferos. 37014 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Reptiles. 371 records from Bannwald Burghauser Forst. 1506 records from (Appendix C) Benthic foraminifera extinction group species in combined ODP Site 162-980 and DSDP Site 80-548. 15 records from Kühnauer Aue und Kühnauer See. 60 records from Pollen and age analysis of terrestrial plant wax from ODP Hole 175-1085A. 93 records from Haarbach Höfe. 106 records from VFD-RP: Eifel: Orchideenweide Ankly. 249 records from BIRDRACE DEVK-Deutschlands Enthusiastischste Vogel Kucker. 161 records from BIRDRACE Nord-Seh-Team. 334 records from BIRDRACE Cuxland - Schwenke Geo Consult. 278 records from BIRDRACE Usedommeln. 254 records from BIRDRACE Thüringer Becken-Birders. 118 records from BIRDRACE Die Lippegeier. 82 records from BIRDRACE Die Ziegeneier. 91 records from BIRDRACE NABU LV Hessen. 91 records from BIRDRACE SchrägeVögel. 95 records from BIRDRACE accipiter hardcore birding. 96 records from BIRDRACE OAG Neuwerk. 100 records from BIRDRACE Lohmanns Öömi-Studenten. 100 records from BIRDRACE Stuttgart 100 trööt. 101 records from BIRDRACE Enger am Spektiv. 102 records from BIRDRACE Westfälische Nachtigallen. 106 records from BIRDRACE Die Göttinger Sozialbrachvögel. 104 records from BIRDRACE Erlanger Piepmätzchen. 106 records from BIRDRACE Ave Goettingen!. 126 records from BIRDRACE Duckehühnchen. 123 records from BIRDRACE Unterste Niederrhein-Rennvögel. 123 records from BIRDRACE INTERNETLITHO feat Fliegende Füchse. 111 records from BIRDRACE Die Wendehälse. 110 records from BIRDRACE Angeliter Ornis. 4500 records from (Figure 7) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-540. 277 records from Naturschutzgebiet Börstig bei Hallstadt. 318 records from 10. GEO - Tag der Artenvielfalt 2008 - LSG "Pfarrhübel" Chemnitz. 61 records from Fürstenberger Ralley Teil 3. 1314 records from Biosphärenpark Wienerwald - Wiener Steinhofgründe. 146 records from LK 11 im Mönchspark. 366 records from Weinberg Reichersdorf. 313 records from BIRDRACE Gätkes Erben. 272 records from BIRDRACE Niederlausitz-Team. 274 records from BIRDRACE Asiola-Quartett. 256 records from BIRDRACE Upupa epöpse. 1 records from Murcia ephippiata. 166 records from BIRDRACE Die Düsselmöwen. 95 records from BIRDRACE BiBi. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Bkassine*. 102 records from BIRDRACE Buteo1DO. 103 records from BIRDRACE Die Otzberger. 149 records from BIRDRACE Birding Bentheim. 60102 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 108 records from BIRDRACE Diesmal sehen wir mehr. 173 records from FFH-Gebiet Klosterwasser/Burkau. 144 records from Lustbach-Umland. 709 records from "Laubenheimer Bodenheimer Ried" - von Stromtalwiesen und Flutrasen. 248 records from Schulgarten der Volksschule. 80 records from Feldweg Waldkirchen. 264 records from Artenvielfalt im Naturschutzgebiet an der Loreley - Leiselfeld/Spitznack - 2. Jahr. 104 records from BIRDRACE Andechser Stativträger. 69 records from Unter hellen Zinnen und finsteren Grotten. 57 records from Schulgarten Janusz-Korczak-Realschule. 2179 records from (Table 7) Absolute abundances of benthic foraminifera in Neogene sediments of DSDP Site 90-588_Site in the southwest Pacific. 61 records from (Table 1) Sedimentology of core D11957P. 26 records from Living benthic foraminifera at station M33/1_MC-25 (EAST), size fraczion 63-125 µm. 22 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 µm. 357 records from Abundance of benthic foraminiferal taxa for the Lower Oligocene of section Poetschbichl in the Lower Inn Valley area. 138 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 169 records from Expedition "Schulgelände". 517 records from Schulzentrum "Parc Hosingen". 74 records from Schulwald Grundschule Brügge. 260 records from (Table T5) Biogenic and mineral composition of sediments cored in Westerland, Sylt. 126 records from Schulwald Marksuhl. 369 records from BIRDRACE Havelland. 145 records from BIRDRACE Dith Marsh Sandpiper. 279 records from BIRDRACE Wannacks Topti(c)ker. 287 records from BIRDRACE Pody und Co. 280 records from BIRDRACE Alb-Donaumoos-Kompetänzteam. 139 records from BIRDRACE Turbine Untersee. 65 records from BIRDRACE Federal Birds of Investigation FBI. 69 records from BIRDRACE Pfeifenten. 157 records from BIRDRACE Rheinische Wasserrallen. 78 records from BIRDRACE leucorhö statt logorrhö. 84 records from BIRDRACE Bielefinken. 96 records from BIRDRACE Emslandracer. 98 records from BIRDRACE Die Paradiesvögel. 99 records from BIRDRACE TEAM BO-BACHTER. 102 records from BIRDRACE Willi goes Birding. 103 records from BIRDRACE federleser. 105 records from BIRDRACE Kiesmätze. 105 records from BIRDRACE coesfelder_vogelkundler. 174 records from BIRDRACE Bon(n)apartemöwen. 132 records from BIRDRACE Die Wetterauer. 115 records from BIRDRACE Die UHULOGEN. 114 records from BIRDRACE Di-Bi-Di-Birder. 114 records from BIRDRACE VIE will rock you!. 112 records from BIRDRACE Gütersloher Gimpel. 109 records from BIRDRACE Die Borner. 121 records from BIRDRACE Immerwiederhopf. 107 records from BIRDRACE Herford Birders. 107 records from BIRDRACE Borussia Zippammer. 402 records from Tag der Artenvielfalt in Heidelberg. 44 records from Wiesen am Treffpunkt Freizeit. 504 records from Schatzinsel Wangerooge. 54 records from Königsdorfer Wald. 73 records from VFD-HH/SH: Pferdweide Lammert. 121 records from Owere Fiddel. 234 records from Wiesen-Wälder-Wasser um Dansenberg, Biosphärenreservat Pfälzerwald. 113 records from Tornoer Teich. 62 records from Lebensraum Dorf. 116 records from Sürther Aue. 132 records from Aachtobel. 447 records from Natur-Erlebnisgebiet der Naturschutz-Akademie Hessen und Umgebung. 112 records from Kaniswall/ Gosener Wiesen an der Spree. 269 records from BIRDRACE Kosmos-Racer. 1087 records from The Bat Conservation Trust - Bechstein's Bat Survey Project. 54 records from Living benthic foraminifera at station M33/1_MC-25 (EAST), size fraction >125 µm. 43 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 63-125 µm. 26 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 30-63 µm. 250 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD Cetacean data up to current day. 16 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-18, 63-125 µm fraction. 541 records from Benthic foraminiferal assamblage in the 125-250 micron fraction of sediment core PS1906-1 (Table 6). 212 records from Benthic foraminifera assemblage in sediment core BBLL3_MC1. 11 records from Balantiocheilos ambusticauda, a new and possibly extinct species of cyprinid fish from Indochina (Cypriniformes: Cyprinidae).. 945 records from (Appendix 6) Benthic foraminifera at termination I in sediment core GIK23414-9 in the Norwegian Sea. 94 records from Distribution of calcareous foraminifers in sediment core Well 6406/8-1. 394 records from Distribution of agglutinated foraminifers in sediment core Well 6406/11-1. 553 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 790 re
Keywords: GBIF; biodiversity; species occurrences